Polarizing plate, method for manufacturing polarizing plate, and display device
By using a polarizer containing specific cellulose acetate in a liquid crystal display device, the problems of color unevenness and contrast fluctuations in high humidity environments are solved, and a more stable display effect is achieved.
Patent Information
- Application Number
- CN202410845452.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-06-27
- Publication Date
- 2024-12-31
AI Technical Summary
When existing liquid crystal display devices are stored or used in high humidity environments, they are prone to problems of color unevenness and contrast fluctuations, mainly due to the uneven phase difference value of the cellulose acetate film in high humidity environments.
Polarized plates with polyester and specific cellulose acetate are used in sequence, and polyester is contained in the first optical film and the second optical film contains cellulose acetate with a degree of acetyl substitution in the range of 2.30 to 2.80, thereby improving the hydrophobicity and increasing the film. Plasticity reduces moisture ingress, thereby suppressing color unevenness and contrast fluctuations.
It effectively suppresses color unevenness and contrast fluctuations caused by water content, and improves the visibility and display quality of the display device.
Smart Images

Figure CN119224908A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate, a method for producing a polarizing plate, and a display device, and more particularly to a polarizing plate capable of suppressing color unevenness and contrast fluctuation caused by water inclusion. Background Art
[0002] In recent years, the use environment of displays (display devices) has become increasingly harsh. In addition, the display is required to be larger and the display quality is improved, and the requirements for displays are getting higher and higher. As a result, the requirements for polarizers in display devices are also getting higher.
[0003] Generally, a polarizing plate includes a polarizer, a protective film for protecting the polarizing plate itself, and other functional films.
[0004] Japanese Patent Document 1 discloses a technology related to a liquid crystal display device having a cellulose ester polarizing plate and protective films A and B. However, when the liquid crystal display device is stored in a high humidity environment, used in a high humidity environment, or used immediately after being taken out of a high humidity environment, there is a problem that color unevenness occurs due to the moisture. In addition, there is a problem that the contrast of the display screen of the liquid crystal display device fluctuates.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Korean Patent Publication No. 10-2017-0081024 Summary of the invention
[0008] The present invention has been made in view of the above problems and circumstances, and aims to provide a polarizing plate, a method for producing a polarizing plate, and a display device capable of suppressing color unevenness and contrast fluctuation caused by water inclusion.
[0009] The present inventors have studied the causes of the above problems in order to solve the above problems. As a result, they have found that in a polarizing plate including a first optical film, a polarizer, and a second optical film in this order, by making the first optical film contain polyester and the second optical film contain a specific polyester and cellulose acetate having a degree of substitution of acetyl groups within a range of 2.30 to 2.80, color unevenness and contrast fluctuation caused by water inclusion can be suppressed, thereby completing the present invention.
[0010] That is, the above-mentioned problems according to the present invention can be solved by the following means.
[0011] 1. A polarizing plate, characterized in that it is a polarizing plate comprising a first optical film, a polarizer and a second optical film in this order,
[0012] The first optical film contains polyester,
[0013] The second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and cellulose acetate having a degree of substitution of acetyl groups within a range of 2.30 to 2.80.
[0014] General formula (I): T-(DP) n -D
[0015] General formula (II): T-(DP) n -DT
[0016] (In the above general formulae (I) and (II), T represents a phenylcarboxylic acid residue.
[0017] D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms.
[0018] P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0019] n represents an integer greater than or equal to 1. )
[0020] 2. The polarizing plate according to item 1, wherein the content of the polyester represented by the general formula (II) is in the range of 70 to 90% by mass relative to the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II).
[0021] 3. The polarizing plate according to item 1, wherein the polyester contained in the first optical film is polyethylene terephthalate.
[0022] 4. The polarizing plate according to item 1, wherein the second optical film further contains an ester represented by the following general formula (III).
[0023] General formula (III): TD
[0024] 5. The polarizing plate according to item 1, wherein the width of the second optical film is in the range of 2.2 to 3.0 m.
[0025] 6. A method for producing a polarizing plate, comprising producing the polarizing plate according to any one of items 1 to 5.
[0026] 7. A display device comprising the polarizing plate according to any one of items 1 to 5,
[0027] The second optical film is disposed on the liquid crystal cell side.
[0028] According to the above means of the present invention, it is possible to provide a polarizing plate, a method for producing a polarizing plate, and a display device capable of suppressing color unevenness and contrast fluctuation caused by water inclusion.
[0029] The mechanism of the effects of the present invention or the mechanism of action is not yet clear, but is presumed as follows.
[0030] Preferably, the polarizing plate of the present invention is provided in a display device. In a display device provided with the polarizing plate of the present invention, the first optical film is arranged outside compared with the second optical film. Here, the "outside" refers to a position closer to the outside air in the display device. The second optical film is arranged closer to the liquid crystal cell than the first optical film.
[0031] In the prior art, if a monochrome image is displayed on a display device stored in a high humidity environment, a uniform monochrome image cannot be displayed, resulting in color unevenness. The cause of the color unevenness is not clear, but one of the causes is believed to be the in-plane unevenness of the phase difference value of the phase difference film.
[0032] Cellulose acetate film is widely used as a phase difference film. However, in a high humidity environment, water molecules are easily coordinated to the hydrophilic groups (carbonyl and hydroxyl groups) of the cellulose acetate molecules, and the phase difference value is easily changed. Therefore, if a display device equipped with a cellulose acetate film as a phase difference film is stored in a high humidity environment, the performance as a phase difference film is reduced.
[0033] A large display device is equipped with a cellulose acetate film having a large area. In a high humidity environment, the cellulose acetate film cannot uniformly absorb moisture over the entire surface due to its large area, and the degree of moisture absorption becomes uneven within the surface. As a result, the retardation value of the cellulose acetate film is not uniform over the entire surface, but becomes uneven. Therefore, it is considered that color unevenness occurs when a monochrome image is displayed on such a display device.
[0034] Therefore, it is believed that by reducing the amount of water reaching the cellulose acetate film in the display device, color unevenness due to water inclusion can be suppressed. In addition, it is believed that even if water reaches the cellulose acetate film, color unevenness due to water inclusion can be suppressed by preventing water molecules from being coordinated to the carbonyl group or hydroxyl group of the cellulose acetate molecules.
[0035] The first optical film contains polyester. Polyester has many hydrophobic sites in its chemical structure. Therefore, the first optical film is not easy to absorb moisture, and can inhibit moisture from entering the interior of the display device. In addition, the amount of moisture reaching the second optical film can be reduced.
[0036] The second optical film contains cellulose acetate having a degree of substitution of acetyl groups in the range of 2.30 to 2.80. In addition, the second optical film contains polyesters represented by the above general formulas (I) and (II) as additives. In this specification, the polyesters represented by the general formulas (I) and (II) are also referred to as "polyester (I)" and "polyester (II)", respectively.
[0037] The two ends of polyester (I) are composed of monocarboxylic acid (T) and diol (D), respectively. That is, there is an unreacted hydroxyl group at one end of polyester (I). Hereinafter, such a structure is also referred to as "single-side end-capping". On the other hand, both ends of polyester (II) are composed of monocarboxylic acid (T). That is, there is no unreacted carboxyl group or hydroxyl group at both ends of polyester (II). Hereinafter, such a structure is also referred to as "double-side end-capping".
[0038] Polyesters (I) and (II) are composed of monocarboxylic acid (T), diol (D) and dicarboxylic acid (P). In the monocarboxylic acid (T), diol (D) and dicarboxylic acid (P) involved in the present invention, the sites other than the carboxyl group and the hydroxyl group are relatively hydrophobic. Therefore, polyesters (I) and (II) are hydrophobic as compounds. By adding a hydrophobic compound to the cellulose acetate film, the degree of hydrophobicity of the entire film can be increased, and it is not easy to absorb water.
[0039] The one-side-capped polyester (I) has a hydroxyl group as a hydrophilic group at one end. The hydroxyl group reacts with water molecules entering the film. The water molecules react with the hydroxyl group of the polyester (I) before reacting with the carbonyl group or hydroxyl group of the cellulose acetate molecules, thereby suppressing the reaction between the cellulose acetate molecules and the water molecules. As a result, the fluctuation of the phase difference value of the film can be suppressed.
[0040] From the viewpoint of increasing the degree of hydrophobicity of the film, it is preferred to add polyester (II) with both ends blocked. However, even if polyester (II) is added, it is still difficult to completely prevent water from entering the film. Therefore, by further adding polyester (I), even if water enters the film, the reaction of water molecules with cellulose acetate can be suppressed. That is, by using polyester (I) and (II) in combination, the change in the phase difference value of the film caused by the reaction of water molecules with cellulose acetate can be fully suppressed. As a result, it is believed that color unevenness caused by water inclusion can be suppressed.
[0041] In addition, by adding polyesters (I) and (II), the intermolecular distance of cellulose acetate becomes larger and the intermolecular force becomes weaker. That is, a plasticizing effect is produced. As a result, in the manufacturing process of the second optical film, the entire film can be stretched uniformly so that the fast axis or slow axis of the film becomes uniform. As a result, it is believed that the fluctuation of the contrast within the surface can be suppressed. It should be noted that polyester (I) can also produce a sufficient plasticizing effect, but polyester (II) can produce a higher plasticizing effect. It is believed that a high plasticizing effect can be obtained by using polyesters (I) and (II) in combination.
[0042] That is, from the viewpoint of improving the hydrophobicity and plasticizing effect of the film, it is considered that it is preferable to add only polyester (II). However, by using polyester (I) in combination, the change of the phase difference value of the film can be fully suppressed. As a result, it is considered that the color unevenness and contrast fluctuation caused by water content can be suppressed, and the visibility of the display device can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a cross-sectional view of the basic layer structure of a polarizing plate.
[0044] Figure 2 It is a schematic diagram showing an example of the configuration of a display device.
[0045] Figure 3 This is a diagram for explaining measurement points in the evaluation of contrast fluctuation.
[0046] Explanation of symbols
[0047] 1 Polarizer
[0048] 2. No. 1 optical film
[0049] 4 Polarizer
[0050] 5. Second optical film
[0051] 100 Display device
[0052] 101A, 101B Polarizer
[0053] 101C LCD unit
[0054] 102A, 102B First optical film
[0055] 103A, 103B, 103C, 103D Adhesive layer
[0056] 104A, 104B Polarizer
[0057] 105A, 105B Second optical film
[0058] 106 Adhesive layer
[0059] 107 Liquid crystal layer
[0060] 108A, 108B Glass substrate DETAILED DESCRIPTION
[0061] The polarizing plate of the present invention is characterized in that it is a polarizing plate comprising a first optical film, a polarizer and a second optical film in sequence, wherein the first optical film contains polyester, and the second optical film contains the polyester represented by the general formula (I), the polyester represented by the general formula (II), and cellulose acetate having a degree of substitution of acetyl groups in the range of 2.30 to 2.80.
[0062] This feature is a common or corresponding technical feature in the following embodiments.
[0063] As an embodiment of the present invention, from the viewpoint of improving the hydrophobicity of the second optical film and suppressing color unevenness, the content of the polyester represented by the general formula (II) is preferably in the range of 70 to 90 mass % relative to the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II).
[0064] As an embodiment of the present invention, from the viewpoint of reducing the amount of water reaching the second optical film and suppressing color unevenness, the polyester contained in the first optical film is preferably polyethylene terephthalate.
[0065] As an embodiment of the present invention, from the viewpoint of preventing water molecules from being coordinated to the hydrophilic groups of the cellulose acetate molecules and suppressing color unevenness, the second optical film preferably contains the ester represented by the general formula (III) at one step.
[0066] As an embodiment of the present invention, from the viewpoint of achieving both high uniformity and productivity in stretching and suppressing fluctuations in contrast, the width of the second optical film is preferably within a range of 2.2 to 3.0 m.
[0067] The method for producing a polarizing plate of the present invention is characterized by producing the above-mentioned polarizing plate.
[0068] The display device of the present invention comprises the polarizing plate, wherein the second optical film is disposed on the liquid crystal cell side.
[0069] Hereinafter, the present invention and its constituent elements, and forms and modes for carrying out the present invention will be described in detail. It should be noted that in the present application, "to" is used to include the numerical values described before and after it as the lower limit and the upper limit.
[0070] 1. Overview of Polarizers
[0071] The polarizing plate of the present invention is characterized in that it is a polarizing plate comprising a first optical film, a polarizer and a second optical film in sequence, wherein the first optical film contains polyester, and the second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and cellulose acetate having a degree of substitution of acetyl groups in the range of 2.30 to 2.80.
[0072] General formula (I): T-(DP) n -D
[0073] General formula (II): T-(DP) n -DT
[0074] (In the above general formulae (I) and (II), T represents a phenylcarboxylic acid residue.
[0075] D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms.
[0076] P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0077] Figure 1 2 is a cross-sectional view of the basic layer structure of the polarizer. The polarizer 1 is provided with the first optical film 2, the polarizer 4 and the second optical film 5 in sequence. The polarizer 1 may further have any layer as required. For example, another layer may be provided between the first optical film 2 and the polarizer 4. In addition, another layer may be provided between the polarizer 4 and the second optical film 5.
[0078] Hereinafter, the first optical film, the second optical film and the polarizer constituting the polarizing plate of the present invention will be described respectively. The polarizing plate of the present invention may have other known functional layers.
[0079] 2. The first optical film
[0080] The first optical film according to the present invention contains polyester. It should be noted that the polyester here is a polyester used as a raw material resin of the film. The first optical film may contain a known additive such as an ultraviolet absorber as required.
[0081] The first optical film according to the present invention may have a single-layer structure or a multi-layer structure, and preferably has a multi-layer structure of three or more layers, wherein the intermediate layer contains an ultraviolet absorber.
[0082] From the viewpoint of adhesion to the polarizer, the first optical film preferably has an easy-adhesion layer on at least one side of the film. The easy-adhesion layer preferably has at least one of polyester resin, polyurethane resin or polyacrylic resin as a main component. Here, "main component" refers to a component that accounts for more than 50% by mass in the solid content constituting the easy-adhesion layer.
[0083] (1) Polyester
[0084] The polyester as the raw material resin has excellent transparency, thermal properties and mechanical properties, and the retardation value of the polyester can be easily controlled by stretching.
[0085] Among them, the polyester is preferably polyethylene terephthalate or polyethylene naphthalate. Polyethylene terephthalate and polyethylene naphthalate have large intrinsic birefringence, and it is easier to obtain a high retardation value even if the film is thin. In particular, the effect of polyethylene naphthalate is significant.
[0086] Polyester is obtained by condensing any dicarboxylic acid and diol.
[0087] Examples of the dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, 2,5-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, diphenylcarboxylic acid, diphenoxyethane dicarboxylic acid, diphenylsulfonecarboxylic acid, anthracene dicarboxylic acid, 1,3-cyclopentane dicarboxylic acid, 1,3-cyclohexane dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, hexahydroterephthalic acid, hexahydroisophthalic acid, malonic acid, dimethylmalonic acid, succinic acid, 3,3-diethylsuccinic acid, glutaric acid, 2,2-dimethylglutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, azelaic acid, dimer acid, sebacic acid, suberic acid, and dodecanedicarboxylic acid.
[0088] Examples of the diol include ethylene glycol, propylene glycol, hexylene glycol, neopentyl glycol, 1,2-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, decanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2-bis(4-hydroxyphenyl)propane, and bis(4-hydroxyphenyl)sulfone.
[0089] The dicarboxylic acid component and the diol component may each be contained alone or in combination of two or more.
[0090] Examples of the polyester obtained include polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate (PEN), etc. Among them, polyethylene terephthalate or polyethylene naphthalate is preferred, and polyethylene terephthalate is more preferred.
[0091] The polyester may contain other copolymer components. From the viewpoint of mechanical strength, the proportion of the copolymer components is preferably 3 mol% or less, more preferably 2 mol% or less, and further preferably 1.5 mol% or less.
[0092] (2) Ultraviolet light absorber
[0093] The first optical film preferably contains an ultraviolet absorber. By containing an ultraviolet absorber, the display device can be protected from ultraviolet damage and excellent weather resistance can be achieved. In particular, the alignment film provided in the liquid crystal cell can be protected from ultraviolet damage.
[0094] Examples of the ultraviolet absorber include cyclic imino ester ultraviolet absorbers, benzotriazole ultraviolet absorbers, benzophenone ultraviolet absorbers, salicylate ultraviolet absorbers, cyanoacrylate ultraviolet absorbers, and triazine ultraviolet absorbers.
[0095] Examples of the cyclic iminoester-based ultraviolet absorber include 2,2′-(1,4-phenylene)bis(4H-3,1-benzo oxazin-4-one), 2-methyl-3,1-benzo Oxazine-4-one, 2-butyl-3,1-benzo Oxazine-4-one, 2-phenyl-3,1-benzo Oxazine-4-one, etc.
[0096] As a benzotriazole ultraviolet absorber, for example, 5-chloro-2-(3,5-di-sec-butyl-2-hydroxyphenyl)-2H-benzotriazole can be cited. In addition, as a benzotriazole ultraviolet absorber, for example, (2-2H-benzotriazole-2-yl)-6-(straight chain and side chain dodecyl)-4-methylphenol can be cited. As a commercial product of a benzotriazole ultraviolet absorber, for example, TINUVIN (registered trademark) series such as "TINUVIN (registered trademark) 109, 171, 234, 326, 327, 328, 928" can be cited (the above are manufactured by BASF).
[0097] Examples of the benzophenone-based ultraviolet absorber include 2-hydroxy-4-benzyloxybenzophenone, 2,4-benzyloxybenzophenone, 2,2′-dihydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, and bis(2-methoxy-4-hydroxy-5-benzoylphenylmethane).
[0098] Examples of the salicylate-based ultraviolet absorber include phenyl salicylate and p-tert-butyl salicylate.
[0099] Examples of the cyanoacrylate-based ultraviolet absorber include 2′-ethylhexyl-2-cyano-3,3-diphenylacrylate and ethyl-2-cyano-3-(3′,4′-methylenedioxyphenyl)-acrylate.
[0100] Examples of the triazine-based ultraviolet absorber include 2-(2'-hydroxy-4'-hexyloxyphenyl)-4,6-diphenyltriazine, etc. Examples of commercially available triazine-based ultraviolet absorbers include "TINUVIN (registered trademark) 477" (manufactured by BASF).
[0101] Among them, the ultraviolet absorber is more preferably a cyclic iminoester ultraviolet absorber or a benzotriazole ultraviolet absorber.
[0102] The content of the ultraviolet absorber is preferably in the range of 0.1 to 10% by mass relative to the total mass of the polyester. By making the content 0.1% by mass or more, the weather resistance of the film can be fully obtained. By making the content 10% by mass or less, the transparency of the film can be fully obtained. The content of the ultraviolet absorber is more preferably in the range of 0.5 to 10% by mass, and more preferably in the range of 1.5 to 5% by mass relative to the total mass of the polyester.
[0103] (3) Method for producing the first optical film
[0104] The first optical film can be manufactured by a known method. Specifically, first, the polyester is melted and extruded into a sheet. Then, the formed non-oriented polyester film is stretched in the longitudinal direction at a temperature above the glass transition temperature of the film using the speed difference of the roller. Thereafter, the polyester film is stretched in the transverse direction using a tenter, heat-treated, and relaxed as needed. Thus, a stretched polyester film (the first optical film) is obtained. The stretched polyester film can be a uniaxially stretched film or a biaxially stretched film.
[0105] The manufacturing conditions for obtaining the polyester film can be appropriately set according to a known method. For example, the longitudinal stretching temperature and the transverse stretching temperature are, for example, in the range of 80 to 130° C., preferably in the range of 90 to 120° C. The longitudinal stretching ratio is, for example, in the range of 1.0 to 3.5 times, preferably in the range of 1.0 to 3.0 times. In addition, the transverse stretching ratio is, for example, in the range of 2.5 to 6.0 times, preferably in the range of 3.0 to 5.5 times.
[0106] The retardation value can be controlled by appropriately setting the stretching ratio, stretching temperature or film thickness. For example, the higher the difference between the stretching ratios of longitudinal stretching and transverse stretching, the lower the stretching temperature, and the thicker the film, the easier it is to increase the retardation value. On the contrary, the lower the difference between the stretching ratios of longitudinal stretching and transverse stretching, the higher the stretching temperature, and the thinner the film, the easier it is to reduce the retardation value.
[0107] In addition, the higher the stretching temperature, the lower the total stretching ratio, the easier it is to reduce the value of the ratio of the retardation value to the thickness direction retardation value (Ro / Rth). On the contrary, the lower the stretching temperature, the higher the total stretching ratio, the easier it is to increase the value of the ratio of the retardation value to the thickness direction retardation value (Ro / Rth). The details of the retardation value are described below. The heat treatment temperature is, for example, in the range of 140 to 240°C, preferably in the range of 170 to 240°C.
[0108] The temperature of the relaxation treatment is, for example, in the range of 100 to 230° C., preferably in the range of 110 to 210° C., and more preferably in the range of 120 to 180° C. The amount of relaxation is, for example, in the range of 0.1 to 20%, preferably in the range of 1 to 10%, and more preferably in the range of 2 to 5%. The temperature and amount of relaxation treatment are preferably set so that the thermal shrinkage rate of the polyester film at 150° C. after the relaxation treatment is 2% or less.
[0109] In the uniaxial stretching treatment and the biaxial stretching treatment, after the transverse stretching, the heat treatment and the stretching treatment can be performed again. Thus, the deformation of the orientation axis such as the curling phenomenon can be alleviated. The maximum value of the deformation of the orientation axis relative to the stretching direction caused by the curling phenomenon is preferably within 30°, more preferably within 15°, and further preferably within 8°. By making the maximum value of the deformation of the orientation axis within 30°, when the polarizer is manufactured in the subsequent process for single-piece processing, the optical characteristics between the single-piece processing can be uniformed.
[0110] Here, "orientation principal axis" refers to the direction of molecular orientation at any point on the stretched polyester film. In addition, the deformation of the orientation principal axis relative to the stretching direction refers to the angle difference between the orientation principal axis and the stretching direction. In addition, its maximum value refers to the maximum value of the value in the vertical direction relative to the long side direction. The orientation principal axis can be measured, for example, using a phase difference film and an optical material inspection device "RETS" (manufactured by Otsuka Electronics Co., Ltd.) or a molecular orientation meter "MOA" (manufactured by Oji Instruments Co., Ltd.).
[0111] From the viewpoint of suppressing the variation of the retardation value, the smaller the uneven thickness of the film, the better. However, if the longitudinal stretch ratio is reduced in order to form a difference in the retardation value, the value of the longitudinal thickness unevenness tends to become higher. The value of the longitudinal thickness unevenness is very high within a certain specific range of the stretch ratio. Therefore, it is preferred to set the film making conditions in a manner that the value of the longitudinal thickness unevenness becomes outside a specific range. Hereinafter, the longitudinal thickness unevenness is also referred to as "thickness unevenness".
[0112] The thickness unevenness is preferably 5.0% or less, more preferably 4.5% or less, further preferably 4.0% or less, and particularly preferably 3.0% or less.
[0113] The thickness unevenness can be measured by any method. For example, a continuous strip sample (length 3 m) can be taken in the flow direction of the film. Then, the thickness of 100 points at 1 cm intervals can be measured using a commercially available measuring instrument to find the maximum thickness (d max ), minimum value (d min ), average value (d). The thickness unevenness [%] can be calculated by the following formula. Examples of commercially available measuring instruments include an electronic micrometer "Millitron 1240" (manufactured by SEIKO-EM Co., Ltd.).
[0114] (Formula) Thickness Unevenness [%] = ((d max -d min ) / d)×100
[0115] The thickness of the stretched polyester film is not particularly limited. The thickness is, for example, in the range of 15 to 300 μm, preferably in the range of 30 to 200 μm, and more preferably in the range of 60 to 80 μm. Within the above range, both thin film and visibility can be achieved.
[0116] As a method for mixing the ultraviolet absorber, a known method can be used. For example, the following method can be cited: first, using a mixing extruder, a dried ultraviolet absorber and a polyester raw material are mixed to make a masterbatch, and then, when making a film, a predetermined masterbatch is mixed with the polyester raw material. It should be noted that the "masterbatch" here refers to a substance obtained by mixing the added ultraviolet absorber into a high concentration. By using a masterbatch, the addition amount of the ultraviolet absorber can be correctly adjusted.
[0117] From the viewpoint of making the ultraviolet absorber uniformly dispersed, the content of the ultraviolet absorber is preferably in the range of 5 to 30 mass % relative to the total mass of the masterbatch. The masterbatch is preferably made using a mixing extruder. It is preferably extruded in the range of 1 to 15 minutes at an extrusion temperature above the melting point of the polyester raw material and below 290°C. By making the extrusion temperature below 290°C, the reduction of the ultraviolet absorber can be suppressed, and the viscosity drop of the masterbatch can be suppressed. In addition, by extruding for more than 1 minute, the ultraviolet absorber can be uniformly dispersed. As needed, stabilizers, color tone adjusters, antistatic agents, etc. can be added to the masterbatch.
[0118] The film of the multilayer structure containing more than 3 layers of ultraviolet light absorber can be manufactured by the following method. As an outer layer, the particles of polyester can be supplied to a known melt lamination extruder alone. As an intermediate layer, after the masterbatch containing ultraviolet light absorber and the particles of polyester are mixed in a specified ratio, they are dried and then supplied to a known melt lamination extruder. It is extruded into a sheet from a slit-shaped die, cooled and solidified on a casting roll, and thus an unstretched film is obtained. That is, use more than 2 extruders, 3-layer manifolds or confluence blocks (for example, confluence blocks with a square confluence portion). Then, the film layers constituting the two outer layers are stacked with the film layers constituting the intermediate layer, and 3 layers of sheets are extruded from the die head, and cooled and solidified on a casting roll.
[0119] From the viewpoint of removing foreign matter contained in the polyester raw material, it is preferred to perform high-precision filtration during melt extrusion. The filter particle size (initial filtration efficiency 95%) of the filter material used in high-precision filtration is preferably 15 μm or less. By making the filter particle size of the filter material 15 μm or less, foreign matter larger than 20 μm can be fully removed.
[0120] The easy-adhesion layer can be formed by the following method.
[0121] The coating liquid used in the formation of the easy-adhesion layer is preferably an aqueous coating liquid containing at least one of a water-soluble or water-dispersible copolyester resin, an acrylic resin and a polyurethane resin. As these coating liquids, for example, Japanese Patent No. 3567927 Gazette, Japanese Patent No. 3589232 Gazette, Japanese Patent No. 3589233 Gazette, Japanese Patent No. 3900191 Gazette, Japanese Patent No. 4150982 Gazette, etc. can be referred to.
[0122] The adhesive layer is obtained by coating the coating liquid on one or both sides of a uniaxially stretched film in the longitudinal direction, drying at 100 to 150°C, and further stretching in the transverse direction. The final coating amount of the adhesive layer is preferably 0.05 to 0.20 g / m 2 By making the coating amount 0.05g / m 2 The above results in sufficient adhesion to the polarizer. 2 When the adhesive layer is provided on both sides of the polyester film, the coating amount of the adhesive layer on both sides may be the same or different. The coating amount of the adhesive layer on each side is set within the above range.
[0123] From the viewpoint of easy slip, the easy bonding layer preferably contains particles. The average particle size of the microparticles is preferably below 2 μm. By making the average particle size of the particles below 2 μm, the particles are not easy to fall off from the easy bonding layer. As particles, for example, inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconium oxide, tungsten oxide, lithium fluoride, and calcium fluoride can be cited. In addition, as particles, organic particles such as styrene, acrylic acid, melamine, benzoguanamine, and silicone can be cited. They can contain one alone or more than two.
[0124] As a method for applying the coating liquid, a known method can be used. As a coating method, for example, reverse roll coating, gravure coating, kiss coating, roller brushing, spraying, air knife coating, wire rod coating, tube scraper method, etc. can be mentioned. These methods can be used alone or in combination of two or more.
[0125] The average particle size of the above-mentioned particles can be measured by the following method.
[0126] Take a picture of the particles using a scanning electron microscope (SEM). At a magnification that allows the size of the smallest particle to be in the range of 2 to 5 mm, measure the maximum particle size (the distance between the two farthest points) of 300 to 500 particles. Then, take the arithmetic mean as the average particle size.
[0127] (4) Physical properties of the first optical film
[0128] (4.1) Delay value
[0129] The retardation values Ro and Rth of the first optical film are defined by the following equations, respectively.
[0130] Formula (i)Ro=(n x -n y )×d
[0131] Formula (ii) Rth = {(n x +n y ) / 2-n z}×d
[0132] (In the above formulas (i) and (ii), n x It represents the refractive index in the direction x where the refractive index is the highest in the in-plane direction of the film. y It represents the refractive index in the direction y orthogonal to the direction x in the in-plane direction of the film. z represents the refractive index in the thickness direction z of the film. d[nm] represents the thickness of the film. )
[0133] The first optical film preferably has a retardation value Ro in the in-plane direction relative to light of a wavelength of 589 nm under an environment of 23°C and 55% RH in the range of 3000 to 30000 nm. By making Ro greater than 3000 nm, the interference color (rainbow unevenness due to the observation angle) when observing the first optical film from an oblique direction can be reduced, and good visibility can be obtained. In addition, by making Ro less than 30000 nm, the thickness of the film can be made thin. Ro is preferably greater than 5000 nm, more preferably greater than 8000 nm, and further preferably greater than 10000 nm.
[0134] The ratio of the retardation values (Ro / Rth) is preferably in the range of 0.2 to 1.2, more preferably in the range of 0.5 to 1.0, and further preferably in the range of 0.6 to 1.0. By making the ratio in the above range, the rainbow unevenness generated based on the viewing angle of the film can be reduced. It should be noted that the retardation values Ro and Rth can be controlled according to the type of polyester, the stretching conditions during film manufacturing, etc.
[0135] Retardation values Ro and Rth for light of wavelength 589 nm can be measured under an environment of 23° C. and 55% RH using an automatic birefringence meter. Examples of the automatic birefringence meter include “Axo Scan (Axo Scan Mueller Matrix Polarimeter)” (manufactured by Axo Matrix).
[0136] (4.2) Thickness
[0137] The thickness of the first optical film is preferably 5 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, and particularly preferably 20 μm or more. By being 5 μm or more, good water resistance and mechanical strength can be obtained. In addition, the thickness of the first optical film is preferably 300 μm or less, more preferably 200 μm or less, further preferably 100 μm or less, and particularly preferably 40 μm or less. By being 100 μm or less, both thin film properties and visibility can be achieved.
[0138] (5) Other functional layers
[0139] The stretched polyester film may have a functional layer with various properties on at least one side. As such a functional layer, for example, a hard coating layer, an anti-glare layer, an anti-reflection layer, a low-reflection layer, a low-reflection anti-glare layer, an anti-reflection anti-glare layer, an anti-static layer, a silicone layer, an adhesive layer, an anti-fouling layer, an anti-fingerprint layer, a hydrophobic layer, a blue light blocking layer, etc. can be cited. From the viewpoint of being able to further improve the uneven color when observed from an oblique direction, the functional layer is preferably an anti-glare layer, an anti-reflection layer, a low-reflection layer, a low-reflection anti-glare layer, or an anti-reflection anti-glare layer.
[0140] When various functional layers are provided, it is preferred that an easy bonding layer is provided on the surface of the stretched polyester film. At this time, from the viewpoint of suppressing the interference caused by reflected light, it is preferred that the refractive index of the easy bonding layer is adjusted to the geometric mean of the refractive index of the functional layer and the refractive index of the stretched polyester film. The adjustment of the refractive index of the easy bonding layer can use a known method. For example, the refractive index can be easily adjusted by making the binder resin of the easy bonding layer contain titanium, zirconium or other metal species.
[0141] The coating liquid used in the formation of the easy-adhesive layer preferably contains at least water-soluble or water-dispersible copolyester, acrylic resin or polyurethane. As coating liquid, for example, water-soluble or water-dispersible copolyester solution, acrylic resin solution, polyurethane solution etc. of recording in Japanese Patent Publication No. 6-81714, Japanese Patent No. 3200929, Japanese Patent No. 3632044, Japanese Patent No. 4547644, Japanese Patent No. 4770971, Japanese Patent No. 3567927, Japanese Patent No. 3589232, Japanese Patent No. 3589233, Japanese Patent No. 3900191, Japanese Patent No. 4150982 etc. can be enumerated.
[0142] 3. Second optical film
[0143] The second optical film according to the present invention contains polyester (I), polyester (II), and cellulose acetate having a degree of substitution of acetyl groups within a range of 2.30 to 2.80.
[0144] (1) Polyester additives
[0145] The second optical film of the present invention contains polyesters (I) and (II). Hereinafter, polyesters (I) and (II) are also collectively referred to as "polyester additives". By making the second optical film contain polyester additives, color unevenness and contrast fluctuations caused by water in the polarizer can be suppressed.
[0146] (1.1) Structure of polyester additives
[0147] The polyesters (I) and (II) are represented by the following general formulas (I) and (II).
[0148] General formula (I): T-(DP) n -D
[0149] General formula (II): T-(DP) n -DT
[0150] In the general formulae (I) and (II), T represents a phenylcarboxylic acid residue.
[0151] D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms.
[0152] P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0153] n represents an integer of 1 or greater.
[0154] In the repeating structure of general formula (I), n D and P may all have the same structure or different structures. In the repeating structure of general formula (II), n D and P may all have the same structure or different structures.
[0155] The D in the repeating structure of the general formula (I) and the D at the terminal may have the same structure or different structures. The D in the repeating structure of the general formula (II) and the D at the terminal may have the same structure or different structures.
[0156] The T at both terminals of the general formula (II) may have the same structure or different structures.
[0157] T, D and P in the general formula (I) and T, D and P in the general formula (II) may have the same structure or different structures. In addition, n in the general formula (I) and n in the general formula (II) may have the same value or different values. However, the structure of the polyester (I) is preferably the same as the structure of the polyester (II) except for one terminal (T). By making the structures of the polyester (I) and the polyester (II) similar, their compatibility is improved, and the effect of the present invention can be significantly obtained.
[0158] In the present invention, the "residue" in the benzene carboxylic acid residue, alkylene glycol residue, arylene glycol residue, oxyalkylene glycol residue, alkylene dicarboxylic acid residue, and arylene dicarboxylic acid residue refers to, for example, a partial structure remaining after removing a lost hydroxyl group or hydrogen atom from the molecular structural formula of benzene carboxylic acid, alkylene glycol, etc. by forming an ester.
[0159] That is, when a monocarboxylic acid is represented by "R-COOH", the monocarboxylic acid residue is represented by "R-CO-". When a dicarboxylic acid is represented by "HOOC-R-COOH", the dicarboxylic acid residue is represented by "-OC-R-CO-". When a diol is represented by "HO-R-OH", the diol residue is represented by "-ORO-" or "-OR-OH".
[0160] T each represents a benzoic acid residue. Examples of benzoic acid include o-methylbenzoic acid, m-methylbenzoic acid, p-methylbenzoic acid, benzoic acid, p-tert-butylbenzoic acid, dimethylbenzoic acid, ethylbenzoic acid, n-propylbenzoic acid, aminobenzoic acid, and acetoxybenzoic acid. Among them, benzoic acid is preferably methylbenzoic acid.
[0161] These may be contained alone or in combination of two or more.
[0162] D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms.
[0163] Examples of the alkylene glycol having a carbon number of 2 to 12 include ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 2,2-dimethyl-1,3-propylene glycol (neopentyl glycol), 2,2-diethyl-1,3-propylene glycol, (3,3-dihydroxymethylpentane), 2-n-butyl-2-ethyl-1,3-propanediol (3,3-dihydroxymethylheptane), 3-methyl-1,5-pentanediol, 1,6-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-ethyl-1,3-hexanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,12-octadecanediol, etc. Among them, propylene glycol or neopentyl glycol is preferred.
[0164] These may be contained alone or in combination of two or more.
[0165] Examples of the arylene diol having 6 to 12 carbon atoms include 1,2-dihydroxybenzene (catechol), 1,3-dihydroxybenzene (resorcinol), and 1,4-dihydroxybenzene (hydroquinone).
[0166] These may be contained alone or in combination of two or more.
[0167] Examples of the oxyalkylene glycol having a carbon number of 4 to 12 include diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, etc. Among them, diethylene glycol, triethylene glycol, or dipropylene glycol is preferred.
[0168] These may be contained alone or in combination of two or more.
[0169] P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms.
[0170] Examples of the alkylene dicarboxylic acid having 4 to 12 carbon atoms include succinic acid, maleic acid, fumaric acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid.
[0171] These may be contained alone or in combination of two or more.
[0172] Examples of the arylene dicarboxylic acid having a carbon number of 6 to 12 include phthalic acid, terephthalic acid, isophthalic acid, 1,5-naphthalene dicarboxylic acid, and 1,4-naphthalene dicarboxylic acid. Among them, phthalic acid is preferred.
[0173] These may be contained alone or in combination of two or more.
[0174] n represents the number of repetitions. It is preferable that n is within the range of 1 to 170.
[0175] The number average molecular weight of the polyester is preferably 20,000 or less, more preferably 10,000 or less. Among them, polyester additives with a number average molecular weight in the range of 400 to 10,000 have good compatibility with cellulose acetate. In addition, polyester additives with a number average molecular weight in the range of 400 to 10,000 are preferred because they are less likely to evaporate or volatilize during film formation. The number average molecular weight of the polyester can be measured by gel permeation chromatography (GPC). Low molecular weight compounds that cannot be measured by GPC are calculated from the structural formula.
[0176] The acid value of the polyester is preferably 0.5 mgKOH / g or less, more preferably 0.3 mgKOH / g or less. The hydroxyl value of the polyester is preferably 25 mgKOH / g or less, more preferably 15 mgKOH / g or less.
[0177] "Acid value" refers to the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. "Hydroxy value" refers to the number of milligrams of potassium hydroxide required to neutralize acetic acid bonded to hydroxyl groups when 1 g of a sample is acetylated. Acid value and hydroxyl value can be measured based on JIS K0070.
[0178] Specific examples of polyester (II) are shown below. However, the present invention is not limited thereto. It should be noted that polyester (I) and ester (III) described below preferably have the same structure as T, D and P in polyester (II) described below.
[0179]
[0180]
[0181]
[0182]
[0183] (1.2) Synthesis method of polyester additives
[0184] The polycondensation of polyester is not particularly limited, and known methods can be used. For example, a direct reaction of a dicarboxylic acid and a diol can be mentioned. In addition, a hot melt condensation method based on a polyesterification reaction or an ester exchange reaction of a dicarboxylic acid or its alkyl ester (e.g., methyl ester) and a diol can be mentioned. In addition, a dehydrohalogenation reaction of a dicarboxylic acid chloride and a diol can be mentioned.
[0185] The polyester with a relatively low number average molecular weight is preferably synthesized by direct reaction. The polyester with a high distribution rate on the low molecular weight side has very high compatibility with cellulose acetate. Moreover, the formed second optical film has low moisture permeability and excellent transparency.
[0186] The method for adjusting the molecular weight is not particularly limited, and known methods can be used. For example, when the ends of the molecules are capped with monocarboxylic acids, the molecular weight can be adjusted by controlling the amount of monocarboxylic acid added. In addition, one-side capping or both-side capping can be selected by controlling the amount of monocarboxylic acid added.
[0187] Consider from such viewpoint, monocarboxylic acid is preferably the material that will not be distilled off outside the system in the polycondensation reaction, and is easily distilled off when removing outside the reaction system after stopping. In addition, the monocarboxylic acid that is not easy to distill off outside the system in the polycondensation reaction and the monocarboxylic acid that is easily distilled off when removing outside the reaction system after stopping can be used in combination.
[0188] In the case of direct reaction, the number average molecular weight can be adjusted by measuring the timing of reaction cessation according to the amount of water distilled off in the polycondensation reaction. In addition, the number average molecular weight can also be adjusted by unbalancing the number of moles of dicarboxylic acid or diols input. In addition, the number average molecular weight can be adjusted by controlling the reaction temperature.
[0189] As an example, a method for synthesizing compound A in which only one side of the molecular terminal is capped with a monocarboxylic acid is described.
[0190]
[0191] (Synthesis of Intermediate 1)
[0192] The following ingredients were dissolved in ethyl acetate.
[0193] Propylene glycol 228.0 parts by mass
[0194] 121.0 parts by mass of triethylamine
[0195] The following components were added while maintaining the temperature of the reaction solution at 50°C or lower.
[0196] Terephthaloyl chloride 101.5 parts by mass
[0197] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution and stirred, and the aqueous layer was removed. The organic layer was further washed with water 4 times. The solvent of the organic layer was distilled off under reduced pressure to obtain Intermediate 1 (127 parts by mass, yield 90%).
[0198] (Synthesis of Compound P11)
[0199] The following ingredients were dissolved in toluene.
[0200] Intermediate 1 71.5 parts by mass
[0201] 30.0 parts by mass of triethylamine
[0202] The following components were added while maintaining the temperature of the reaction solution at 50°C or lower.
[0203] 19.3 parts by mass of p-toluoyl chloride
[0204] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution and stirred, and the aqueous layer was removed. The organic layer was further washed twice with a 5% sodium carbonate aqueous solution. After the organic layer was washed with saturated brine, it was concentrated under reduced pressure. The obtained residue was purified by silica gel column chromatography to obtain compound A (37.5 parts by mass, yield 75%).
[0205] (1.3) Content of polyester additives
[0206] The total content of the polyester additive is preferably in the range of 1 to 40% by mass, more preferably in the range of 2 to 30% by mass, and even more preferably in the range of 3 to 15% by mass, relative to the total mass of the second optical film.
[0207] The content of the polyester (II) is preferably in the range of 70 to 90% by mass relative to the total mass of the polyester (I) and the polyester (II). Within the above range, color unevenness due to water inclusion can be further suppressed.
[0208] (1.4) Low molecular weight esters
[0209] The second optical film according to the present invention preferably contains an ester (III). The ester (III) is represented by the following general formula (III).
[0210] General formula (III): TD
[0211] It should be noted that T and D in the general formula (III) have the same meanings as T and D in the above-mentioned general formulas (I) and (II).
[0212] The structure of the polyester (III) is preferably the same as the structure obtained by removing the repeating structure in the polyester (I). By making the structures of the polyester (I) and the polyester (III) similar, their compatibility is improved, and the effects of the present invention can be significantly obtained.
[0213] The content of the ester (III) is preferably in the range of 0.1 to 10 mass %, more preferably in the range of 0.2 to 8 mass %, and even more preferably in the range of 0.3 to 5 mass %, relative to the total mass of the second optical film.
[0214] The relationship between polyester (I), polyester (II) and ester (III) is shown below.
[0215] Water resistance effect: ester (III) < polyester (I) < polyester (II)
[0216] Plasticizing effect: ester (III) < polyester (I) < polyester (II)
[0217] Ease of movement: Polyester (II) < Polyester (I) < Ester (III)
[0218] The higher the ratio of the hydrophobic part to the hydrophilic part in the molecule of these compounds, the more hydrophobic the molecule is and the higher the water resistance is. The film containing the compound with high water resistance is less likely to absorb water into the film and the phase difference value of the film is less likely to change.
[0219] The larger the molecular weight of these compounds, the higher the plasticizing effect. When a film contains a compound with a high plasticizing effect, the film can be stretched uniformly, and the fast axis or slow axis of the film can be made uniform.
[0220] The smaller the molecular weight of these compounds, the easier they are to move freely in the membrane. By making the membrane contain a compound having a hydrophilic group and being easy to move, water molecules can be coordinated to the compound first, thereby preventing water molecules from being coordinated to the hydrophilic groups of cellulose acetate molecules.
[0221] That is, by further containing the ester (III), it is possible to further prevent water molecules from being coordinated to the hydrophilic groups of the cellulose acetate molecules, and to further suppress the fluctuation of the retardation value of the film.
[0222] (2) Cellulose acetate
[0223] Cellulose is a polymer composed of β-glucose linked in a straight chain via β-1,4-glycosidic bonds. Cellulose ester is a cellulose in which some or all of the hydrogen atoms in the hydroxyl groups (-OH) at the 2nd, 3rd, and 6th positions in one glucose unit are replaced by acyl groups. Cellulose esters in which the acyl groups are acetyl groups are called "cellulose acetate".
[0224] The degree of substitution of acetyl groups in the cellulose acetate according to the present invention is in the range of 2.30 to 2.80. The degree of substitution is preferably in the range of 2.40 to 2.70. By setting the degree of substitution in the above range, a desired retardation value can be obtained.
[0225] (Degree of substitution of acetyl group)
[0226] The degree of substitution with acetyl groups indicates the average number of acetyl groups per glucose unit, that is, how many hydrogen atoms of the hydroxyl groups at the 2nd, 3rd, and 6th positions in one glucose unit are substituted with acetyl groups.
[0227] Therefore, the maximum value of the degree of substitution with the acetyl group is 3.0, which means that all the hydrogen atoms of the hydroxyl groups at the 2-, 3-, and 6-positions are substituted with acetyl groups.
[0228] The acetyl group may be substituted evenly at the 2-position, 3-position, and 6-position in one glucose unit, or may be substituted in a distributed manner.
[0229] The degree of substitution of acetyl groups can be determined by the method specified in ASTM-D817-96.
[0230] From the viewpoint of obtaining desired optical properties, cellulose acetates having different degrees of substitution may be used in combination. The mixing ratio of cellulose acetates having different degrees of substitution is not particularly limited.
[0231] From the viewpoint of mechanical strength, the number average molecular weight (Mn) of cellulose acetate is preferably 2×10 4 ~3×10 5 In the range of 2×10 4 ~1.2×10 5 In the range of 4×10 4 ~8×10 4 within the range.
[0232] From the viewpoint of mechanical strength, the weight average molecular weight (Mw) of cellulose acetate is preferably 2×10 4 ~1×10 6 In the range of 2×10 4 ~1.2×10 5 In the range of 4×10 4 ~8×10 4 within the range.
[0233] The number average molecular weight (Mn) and weight average molecular weight (Mw) of cellulose acetate can be measured by the following method.
[0234] <Gel Permeation Chromatography>
[0235] Solvent: Dichloromethane
[0236] Column: Connect three Shodex K806, K805, K803G (all manufactured by Showa Denko K.K.)
[0237] Column temperature: 25°C
[0238] Sample concentration: 0.1 mass%
[0239] Detector: RI Model 504 (manufactured by GL Sciences)
[0240] Pump: L6000 (manufactured by Hitachi, Ltd.)
[0241] Flow rate: 1.0mL / min
[0242] Calibration curve: A calibration curve prepared from 13 samples of standard polystyrene STK standard polystyrene (manufactured by TOSOH Corporation) in the range of Mw = 500 to 2,800,000 is used. The 13 samples are preferably used at substantially equal intervals.
[0243] Cellulose acetate can be synthesized by a known method.
[0244] The raw material cellulose of cellulose acetate is not particularly limited, and examples thereof include cotton linters, wood pulp, kenaf, and the like. The raw material cellulose, acetic acid, acetic anhydride, and a catalyst (such as sulfuric acid) are mixed to esterify the cellulose. It should be noted that the reaction is carried out to such an extent that triesters of cellulose can be formed. In triesters, the hydrogen atoms of the three hydroxyl groups in one glucose unit are all replaced by acetyl groups.
[0245] Next, cellulose acetate having a desired degree of acetyl substitution is obtained by hydrolyzing the triester of cellulose.
[0246] Thereafter, cellulose acetate is finally obtained through the steps of filtration, precipitation, water washing, dehydration, drying, etc. Specifically, it can be synthesized with reference to the method described in Japanese Patent Application Laid-Open No. 10-45804.
[0247] Examples of commercially available products of cellulose acetate include "LM80, L20, L30, L40, and L50" (all manufactured by DAICEL), and "Ca398-3, Ca398-6, Ca398-10, Ca398-30, and Ca394-60S" (all manufactured by Eastman Chemical).
[0248] (3) Other additives
[0249] The second optical film may further contain additives as required. Examples of the additives include sugar esters, acrylic polymers, plasticizers, and fine particles. In addition, the second optical film may contain the above-mentioned ultraviolet absorber.
[0250] (3.1) Sugar esters
[0251] The second optical film can adjust the retardation value of the film by containing the sugar ester.
[0252] Examples of the sugar ester include compounds obtained by esterifying all or part of the hydroxyl groups (—OH) in the compound (A) having one furanose structure or pyranose structure with an aliphatic acyl group.
[0253] Examples of the sugar ester include compounds obtained by esterifying all or part of the hydroxyl groups (—OH) in the compound (B) in which 2 to 12 at least one of furanose structures or pyranose structures are bonded with an aliphatic acyl group.
[0254] Preferred examples of the compound (A) and the compound (B) include the compounds shown below, but the present invention is not limited to these examples.
[0255] Examples of the compound (A) include glucose, galactose, mannose, fructose, xylose, arabinose, etc. The compound (A) may contain maltitol obtained by hydrogenation reduction of maltose under high pressure.
[0256] Examples of the compound (B) include lactose, sucrose, cellobiose, maltose, cellotriose, maltotriose, raffinose, and ketose.
[0257] Among them, the compound preferably has both a furanose structure and a pyranose structure. Examples of the compound having both a furanose structure and a pyranose structure include sucrose.
[0258] The monocarboxylic acid used in synthesizing the sugar ester is not particularly limited, and examples thereof include known aliphatic monocarboxylic acids, alicyclic monocarboxylic acids, etc. The monocarboxylic acid may be used alone or in combination of two or more.
[0259] Examples of the aliphatic monocarboxylic acid include acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, 2-ethylhexanecarboxylic acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, tetracosanoic acid, cerotic acid, heptacosanoic acid, montanic acid, triacontanoic acid, dodecanoic acid and the like; and unsaturated fatty acids such as undecylenic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, octenic acid and the like.
[0260] Examples of the alicyclic monocarboxylic acid include cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, cyclooctanecarboxylic acid, and derivatives thereof.
[0261] The synthesis methods of these compounds can be referred to, for example, Japanese Patent Application Laid-Open No. 8-245678.
[0262] As the sugar ester, an esterified compound of an oligosaccharide in which 3 to 12 of at least one of furanose structures or pyranose structures are bonded can also be used.
[0263] Oligosaccharides are produced by reacting starch, sucrose, etc. with enzymes such as amylase. As oligosaccharides, maltooligosaccharides, isomaltooligosaccharides, fructooligosaccharides, galacto-oligosaccharides, and xylo-oligosaccharides can be mentioned. Oligosaccharides can also be acetylated by the same method as the above-mentioned compound (A) and compound (B).
[0264] An example of the synthesis of sugar esters is shown. Pyridine (100 mL) is added to glucose (29.8 g, 166 mmol) to prepare a solution. Acetic anhydride (200 mL) is added dropwise to the solution and reacted for 24 hours. Thereafter, the solution is concentrated by evaporation, and the concentrate is put into ice water. After the concentrate is left for 1 hour, it is filtered with a glass filter to separate the solid from the water. The solid on the glass filter is dissolved in chloroform and separated with cold water until the solution becomes neutral. After the organic layer is separated, the organic layer is dried using anhydrous sodium sulfate. After removing anhydrous sodium sulfate from the organic layer by filtration, the chloroform is removed by evaporation. Then, the remaining reaction product is further dried under reduced pressure to obtain glucose pentaacetate (58.8 g, 150 mmol, 90.9%). It should be noted that the above-mentioned monocarboxylic acid can be used instead of the above-mentioned acetic anhydride.
[0265] Although specific examples of the sugar ester compound that can be used in the present invention are given below, the present invention is not limited thereto.
[0266]
[0267]
[0268]
[0269]
[0270]
[0271] The content of the sugar ester is preferably in the range of 1 to 35% by mass, more preferably in the range of 5 to 30% by mass, relative to the total mass of the second optical film. By being within the above range, the degradation of the polarization function of the polarizer can be suppressed, and the display quality of the display device can be stabilized. In addition, even if the raw film of the second optical film is stored in a stacked roll state, it is not easy to cause bleeding.
[0272] Sugar esters in which all OH groups are esterified and sugar esters in which more than one OH group remains can be used together. As a combination of sugar esters, for example, a mixture of sucrose octaacetate, sucrose heptaacetate and sucrose hexaacetate can be mentioned. The mixing ratio is not particularly limited, and for example, combinations such as 30:30:30, 40:30:30, 40:50:10, 50:30:20, 60:30:10, 80:10:10, 90:7:3, 95:5:0 can be mentioned. The mixing ratio can be controlled by adjusting the reaction time during the esterification of the sugar or the amount of monocarboxylic acid added to react with the sugar.
[0273] (3.2) Acrylic polymer
[0274] The second protective film contains an acrylic polymer to adjust the phase difference of the film. The number average molecular weight of the acrylic polymer is preferably in the range of 500 to 30000. As such an acrylic polymer, reference can be made to paragraphs
[0059] to
[0093] of International Publication No. 2008 / 044463.
[0275] (3.3) Plasticizer
[0276] The second optical film contains a plasticizer, so that the entire film is stretched uniformly, and the fast axis or slow axis of the film becomes uniform. As a result, in the display device, the fluctuation of the contrast within the surface can be suppressed. In addition, the second optical film contains a plasticizer, and the phase difference value can be adjusted.
[0277] The plasticizer is not particularly limited, and examples thereof include polycarboxylic acid ester plasticizers, glycolic acid ester plasticizers, phthalic acid ester plasticizers, fatty acid ester plasticizers, polyol ester plasticizers, polyester plasticizers, and acrylic plasticizers.
[0278] The glycolate plasticizer is not particularly limited, but alkylphthalyl alkyl glycolates are preferred. Examples of the alkyl phthaloyl alkyl glycolates include methyl phthaloyl methyl glycolate, ethyl phthaloyl ethyl glycolate, propyl phthaloyl propyl glycolate, butyl phthaloyl butyl glycolate, octyl phthaloyl octyl glycolate, methyl phthaloyl ethyl glycolate, ethyl phthaloyl methyl glycolate, ethyl phthaloyl propyl glycolate, methyl phthaloyl butyl glycolate, ethyl phthaloyl butyl glycolate, butyl phthaloyl methyl glycolate, butyl phthaloyl ethyl glycolate, propyl phthaloyl butyl glycolate, butyl phthaloyl propyl glycolate, methyl phthaloyl octyl glycolate, ethyl phthaloyl octyl glycolate, octyl phthaloyl methyl glycolate, and octyl phthaloyl ethyl glycolate.
[0279] Examples of the phthalate plasticizer include diethyl phthalate, dimethoxyethyl phthalate, dimethyl phthalate, dioctyl phthalate, dibutyl phthalate, di-2-ethylhexyl phthalate, dioctyl phthalate, dicyclohexyl phthalate, and dicyclohexyl terephthalate.
[0280] Examples of the citrate plasticizer include acetyl citrate trimethyl, acetyl citrate triethyl, and acetyl citrate tributyl.
[0281] Examples of the fatty acid ester plasticizer include butyl oleate, methyl acetyricinoleate, and dibutyl sebacate.
[0282] Examples of the phosphate ester plasticizer include triphenyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, octyl diphenyl phosphate, diphenyl biphenyl phosphate, trioctyl phosphate, and tributyl phosphate.
[0283] (3.3.1) Polycarboxylic acid ester plasticizers
[0284] Examples of polycarboxylic acid esters include esters of polycarboxylic acids having a valence of 2 or more, preferably 2 to 20, and alcohols. The valence of the polycarboxylic acid is preferably in the range of 2 to 20 for aliphatic polycarboxylic acids, and in the range of 3 to 20 for aromatic polycarboxylic acids and alicyclic polycarboxylic acids.
[0285] The polycarboxylic acid is represented by the following general formula (IV).
[0286] General formula (IV): R2(COOH) m (OH) n
[0287] In the above general formula (IV), R2 represents an organic group with a valence of (m+n), m represents a positive integer greater than 2, n represents an integer greater than 0, the COOH group represents a carboxyl group, and the OH group represents an alcoholic or phenolic hydroxyl group.
[0288] The polycarboxylic acid is not particularly limited, and examples thereof include trivalent or higher aromatic polycarboxylic acids or derivatives thereof (e.g., trimellitic acid, trimesic acid, pyromellitic acid), aliphatic polycarboxylic acids (e.g., succinic acid, adipic acid, azelaic acid, sebacic acid, oxalic acid, fumaric acid, maleic acid, tetrahydrophthalic acid), hydroxy polycarboxylic acids (e.g., tartaric acid, tartronic acid, malic acid, citric acid), etc. Among them, hydroxy polycarboxylic acids are preferred from the viewpoint of improving retention.
[0289] In a high temperature and high humidity environment, additives such as plasticizers are easily precipitated outside the film or volatilized, and as a result, the mass of the film is easily reduced. In the present invention, "retention" refers to the property of inhibiting the precipitation or volatilization of additives outside the film and keeping the additives in the film. Specifically, the mass of the sample is measured after being placed in an environment of 23°C and 55% RH for 1 day. Next, the mass of the sample is measured after being placed in an environment of 80°C and 90% RH for 2 weeks and further placed at 23°C and 55% RH for 1 day. The change ratio of the mass of these samples is calculated and used as a measure of retention. The smaller the change ratio of the mass, the higher the retention can be judged.
[0290] The alcohol is not particularly limited, and examples thereof include known alcohols or phenols. Examples of the alcohol include linear or side-chain aliphatic saturated alcohols or aliphatic unsaturated alcohols having a carbon number of 1 to 32. The carbon number is preferably in the range of 1 to 20, more preferably in the range of 1 to 10. In addition, examples of the alcohol include alicyclic alcohols (cyclopentanol, cyclohexanol, etc.) or derivatives thereof, aromatic alcohols (benzyl alcohol, cinnamyl alcohol, etc.) or derivatives thereof, and the like.
[0291] The alcohol may be used alone or in combination of two or more.
[0292] When a hydroxypolycarboxylic acid is used as the polycarboxylic acid, the alcoholic or phenolic hydroxyl groups of the hydroxypolycarboxylic acid may be esterified with a monocarboxylic acid. The monocarboxylic acid is not particularly limited, and examples thereof include the following compounds.
[0293] Examples of the aliphatic monocarboxylic acid include linear or side-chain fatty acids having carbon atoms of 1 to 32. The number of carbon atoms is preferably in the range of 1 to 20, more preferably in the range of 1 to 10.
[0294] Examples of the aliphatic monocarboxylic acid include saturated fatty acids (acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, heptanoic acid, octanoic acid, nonanoic acid, decanoic acid, 2-ethyl-hexanecarboxylic acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, tetracosanoic acid, cerotic acid, heptadecanoic acid, montanic acid, triacontanoic acid, triacontanoic acid, and dodecanoic acid); and unsaturated fatty acids (undecenoic acid, oleic acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, and the like).
[0295] Examples of the alicyclic monocarboxylic acid include cyclopentanecarboxylic acid, cyclohexanecarboxylic acid, cyclooctanecarboxylic acid, and derivatives thereof.
[0296] Examples of the aromatic monocarboxylic acid include benzoic acid, aromatic monocarboxylic acids obtained by introducing an alkyl group into the benzene ring of benzoic acid (such as methylbenzoic acid), aromatic monocarboxylic acids having two or more benzene rings (such as bibenzoic acid, naphthoic acid, and tetrahydronaphthoic acid), and derivatives thereof.
[0297] Among them, the monocarboxylic acid is preferably acetic acid, propionic acid or benzoic acid.
[0298] The molecular weight of the polycarboxylic acid ester is not particularly limited, but is preferably in the range of 300 to 1000, more preferably 350 to 750. From the viewpoint of improving retention, the larger the molecular weight, the better, and from the viewpoint of moisture permeability and compatibility with cellulose acetate, the smaller the molecular weight, the better.
[0299] The acid value of the polyvalent carboxylic acid ester is preferably 1 mgKOH / g or less, and more preferably 0.2 mgKOH / g or less. When the acid value is within the above range, environmental fluctuations in the retardation value can be suppressed.
[0300] Examples of polycarboxylic acid esters are shown below, but the present invention is not limited thereto. Examples of polycarboxylic acid esters include triethyl citrate, tributyl citrate, acetyl triethyl citrate (abbreviated as ATEC), acetyl tributyl citrate (abbreviated as ATBC), benzoyl tributyl citrate, acetyl triphenyl citrate, acetyl tribenzyl citrate, dibutyl tartrate, diacetyl dibutyl tartarate, tributyl trimellitate, and tetrabutyl pyromellitate.
[0301] (3.4) Particles
[0302] The second protective film can improve the lubricity of the film surface by containing microparticles. In addition, when the films are overlapped, it is possible to suppress damage or close adhesion between the films. In the present invention, "microparticles" refer to particles with an average primary particle diameter of 5 to 400 nm.
[0303] The fine particles may be inorganic fine particles or organic fine particles.
[0304] As inorganic particles, for example, silicon dioxide, titanium dioxide, aluminum oxide, zirconium oxide, calcium carbonate, talc, clay, calcined kaolin, etc. can be cited. In addition, as inorganic particles, for example, calcined calcium silicate, hydrated calcium silicate, aluminum silicate, magnesium silicate, calcium phosphate, etc. can be cited. From the viewpoint of lowering turbidity, the inorganic particles preferably contain silicon, and among them, silicon dioxide is preferred.
[0305] Commercially available silica particles may be used, such as Aerosil (registered trademark) R972, R972V, R974, R812, 200, 200V, 300, R202, OX50, and TT600 (all manufactured by Nippon Aerosil Co., Ltd.).
[0306] Commercially available zirconium oxide fine particles may be used. Examples of commercially available zirconium oxide fine particles include "Aerosil (registered trademark) R976 and R811" (both manufactured by Nippon Aerosil Co., Ltd.).
[0307] As the polymer constituting the organic microparticles, for example, silicone resin, fluororesin and acrylic resin can be cited. Among them, the polymer is preferably silicone resin, and particularly preferably silicone resin having a three-dimensional network structure. Microparticles of silicone resin can use commercial products. As commercial products, for example, "Tosperal (registered trademark) 103, Tosperal 105, Tosperal 108, Tosperal 120, Tosperal 145, Tosperal 3120 and Tosperal 240" (the above are made by Toshiba Silicone Co., Ltd.) can be cited.
[0308] Among them, the fine particles are preferably "Aerosil (registered trademark) 200V" or "Aerosil (registered trademark) R972V". By including these fine particles, the friction coefficient can be sufficiently reduced while keeping the haze of the second optical film low. The dynamic friction coefficient of at least one surface of the second optical film is preferably in the range of 0.2 to 1.0.
[0309] The average particle size of the primary particles of the microparticles is preferably in the range of 10 to 300 nm. The microparticles may be contained in the form of secondary agglomerates with a particle size in the range of 0.05 to 0.3 μm. Preferably, the microparticles are contained in the form of primary particles in which the particles are not agglomerated and have an average particle size in the range of 100 to 400 nm.
[0310] The content of the fine particles is preferably in the range of 0.01 to 1% by mass, more preferably in the range of 0.05 to 0.5% by mass, relative to the total mass of the second optical film.
[0311] (4) Method for manufacturing the second optical film
[0312] The second optical film may be produced by a solution casting method or a melt casting method, among which the solution casting method is preferred.
[0313] The method of manufacturing a film by solution casting includes the following steps: a step of preparing a coating, a step of casting the coating on a metal support, a step of drying a wet film, and a step of peeling the film from the metal support. In addition, the method of manufacturing a film by solution casting includes the following steps: a step of stretching or maintaining the width of the peeled film, a step of further drying the film, and a step of winding the completed film.
[0314] (4.1) Process for preparing coating
[0315] In the step of preparing the coating, cellulose acetate and additives are dissolved in a solvent to prepare the coating. The higher the concentration of cellulose acetate in the coating, the smaller the drying load after casting on the metal support, which is preferred. In addition, by making the concentration of cellulose acetate not too high, the pressure load during filtration can be suppressed, and good filtration accuracy can be obtained. From these viewpoints, the content of cellulose acetate is preferably in the range of 10 to 35% by mass, more preferably in the range of 15 to 25% by mass, relative to the total mass of the coating.
[0316] The solvent used in the preparation of the coating may be a single type or two or more types. However, from the viewpoint of production efficiency, it is preferred to mix a good solvent and a poor solvent for cellulose acetate, and from the viewpoint of the solubility of cellulose acetate, the more good solvent, the better. The mixing ratio of the good solvent to the poor solvent is preferably in the range of 70 to 98% by mass of the good solvent and in the range of 2 to 30% by mass of the poor solvent. It should be noted that a solvent that dissolves cellulose acetate alone is defined as a "good solvent", and a solvent that swells or does not dissolve cellulose alone is defined as a "poor solvent".
[0317] There are no particular restrictions on the good solvent, and examples thereof include organic halides (such as dichloromethane), dioxolanes, acetone, methyl acetate, methyl acetoacetate, etc. Among them, dichloromethane or methyl acetate is preferred. There are no particular restrictions on the poor solvent, and examples thereof include methanol, ethanol, n-butanol, cyclohexane, cyclohexanone, etc.
[0318] The coating material preferably contains water in a range of 0.01 to 2% by mass. The solvent used for dissolving cellulose acetate may be a solvent that recovers the solvent removed from the film by drying and reuses it. The recovered solvent may contain a trace amount of additives (e.g., plasticizer, ultraviolet absorber, polymer, monomer component, etc.). The recovered solvent may be reused even if it contains additives. If necessary, the recovered solvent may be purified and reused.
[0319] The method for dissolving cellulose acetate when preparing the coating material can be a known method. For example, if a heating method and a pressurizing method are combined, the coating material can be heated to a temperature higher than the boiling point under normal pressure. If the solvent is heated and stirred to dissolve the cellulose acetate at a temperature higher than the boiling point under normal pressure and in a range where the solvent does not boil under pressure, the generation of bulky undissolved matter (gel or powder mass) can be prevented. Alternatively, cellulose acetate can be mixed with a poor solvent to wet or swell the cellulose acetate, and then a good solvent can be added to dissolve the cellulose acetate.
[0320] Examples of the pressurization method include a method of pressurizing an inert gas such as nitrogen into the dissolution container, a method of increasing the vapor pressure of the solvent by heating, etc. Heating is preferably performed from the outside, and for example, jacket-type heating is preferred because temperature control is easy.
[0321] From the viewpoint of the solubility of cellulose acetate, the higher the heating temperature, the better. In addition, by not making the heating temperature too high, the pressure burden can be suppressed and good productivity can be obtained. From these viewpoints, the heating temperature is preferably in the range of 45 to 120° C., more preferably in the range of 60 to 110° C., and even more preferably in the range of 70 to 105° C. The pressure is adjusted so that the solvent does not boil at the set temperature.
[0322] Another method for dissolving cellulose acetate is a cooling dissolution method. Cellulose acetate can be dissolved in a solvent such as methyl acetate by the cooling dissolution method.
[0323] The cellulose acetate solution is filtered using a suitable filter material such as filter paper. From the viewpoint of removing insoluble matter, the smaller the absolute filtration accuracy of the filter material, the better. In addition, by making the absolute filtration accuracy not too small, clogging of the filter material can be suppressed. From these viewpoints, the absolute filtration accuracy of the filter material is preferably 0.008 mm or less, more preferably in the range of 0.001 to 0.008 mm, and further preferably in the range of 0.003 to 0.006 mm.
[0324] The material of the filter material is not particularly limited, and known filter materials can be used. From the viewpoint of preventing fiber shedding, the filter material is preferably made of plastic (polypropylene, Teflon (registered trademark), etc.) or metal (stainless steel, etc.). Impurities contained in the raw material cellulose acetate, especially bright spot foreign matter, can be removed or reduced by filtering.
[0325] Two polarizers are arranged in a crossed Nicol prism state, and a second optical film is placed between them. Then, light is irradiated from one polarizer side and observed from the other polarizer side. At this time, the point where light leakage is observed from the opposite side is called a "bright spot foreign body". The number of bright spots with a diameter of 0.01 mm or more is preferably 200 / cm 2 Below, more preferably 100 pieces / cm 2The number of bright spots with a diameter of 0.01 mm or more is more preferably 50 / cm 2 Below, particularly preferably 0 to 10 pieces / cm 2 In addition, the fewer the number of bright spots with a diameter of 0.01 mm or less, the better.
[0326] The coating can be filtered using a known method. Among them, a method of filtering while heating the solvent at a temperature above the boiling point at normal pressure and in a range where the solvent does not boil under pressure is preferred. In this method, the increase in the filtration pressure difference (pressure difference) before and after filtration is small. The heating temperature is preferably in the range of 45 to 120°C, more preferably in the range of 45 to 70°C, and further preferably in the range of 45 to 55°C.
[0327] The filtration pressure is preferably 1.6 MPa or less, more preferably 1.2 MPa or less, and even more preferably 1.0 MPa or less.
[0328] Various additives may be added in batches or in-line by preparing a separate additive solution. In particular, when adding microparticles to the coating, it is preferred to add part or all of the microparticles in-line from the perspective of reducing the burden of the microparticles on the filter material.
[0329] When the additive solution is added in-line, it is preferred to add a small amount of cellulose acetate to the additive solution in advance to dissolve it from the viewpoint of compatibility with the coating material. The amount of cellulose acetate added is preferably in the range of 1 to 10% by mass, more preferably in the range of 3 to 5% by mass, relative to the total mass of the solvent.
[0330] Online addition and mixing can be performed using, for example, a static mixer, an inline mixer, etc. As a static mixer, a mixer manufactured by Toray Engineering Co., Ltd. can be cited. As an inline mixer, Toray static pipeline mixer "Hi-Mixer SWJ" (manufactured by Toray Engineering Co., Ltd.) can be cited.
[0331] (4.2) Step of casting the coating on a metal support
[0332] In the process of casting the coating on the metal support, the coating is cast on the endless metal support that moves infinitely. It is preferred that the surface of the metal support in the casting (casting) process is mirror-finished. The metal support is preferably a stainless steel belt or a drum whose surface is plated by casting. The casting width is preferably in the range of 1 to 4 m, for example.
[0333] (4.3) Process of drying the wet film
[0334] In the step of drying the wet film, the coating material cast on the metal support is dried to form a wet film.
[0335] The surface temperature of the metal support is preferably within a range of -50°C or more and below the boiling point of the solvent. The higher the surface temperature, the faster the drying speed of the wet film. In addition, by making the surface temperature not too high, the foaming of the wet film can be prevented, and good film flatness can be obtained. From these viewpoints, the surface temperature is preferably within a range of 0 to 40°C, more preferably within a range of 5 to 30°C. In addition, the wet film can be gelled by cooling the metal support, and the film can be peeled off from the drum in a state containing a large amount of residual solvent.
[0336] As a method for controlling the temperature of the metal support, there is no particular limitation, for example, a method of blowing warm air or cold air can be cited. In addition, a method of contacting the back side of the metal support with warm water can be cited. The method using warm water can efficiently transfer heat, so the time for the temperature of the metal support to reach a certain value can be shortened. When using warm air, wind with a temperature higher than the target temperature of the metal support can be used.
[0337] (4.4) Step of peeling the film from the metal support
[0338] From the viewpoint of obtaining good planarity of the film, the residual solvent amount when the metal support glass film (wet film) is preferably in the range of 10 to 150 mass %. The residual solvent amount is more preferably in the range of 10 to 40 mass % or 60 to 130 mass %, and further preferably in the range of 10 to 30 mass % or 70 to 120 mass %. Here, the residual solvent amount is defined by the following formula.
[0339] Residual solvent amount [mass %] = {(MN) / N} × 100
[0340] In the formula, M is the mass of the wet film or film sample. N is the mass of the wet film or film sample after heating at 115° C. for 1 hour. It should be noted that the wet film or film sample can be collected at any time during or after the production.
[0341] (4.5) Step of stretching or maintaining the width of the peeled film
[0342] In the process of stretching or maintaining the width of the peeled film, the film with a large amount of residual solvent just after peeling is stretched or maintained in width. It is preferred to adopt a tentering method in which the film is stretched in the conveying direction (longitudinal direction) and the two ends of the film are further held by cloth clips or the like. In addition, it is possible to stretch in the conveying direction (longitudinal direction) and the width direction (transverse direction) at the same time.
[0343] In the longitudinal stretching, the peel tension is preferably 210 N / m or more, more preferably in the range of 220 to 300 N / m.
[0344] The stretching step can control the refractive index of the film and the retardation values Ro and Rth.
[0345] The final stretch ratio in the conveying direction is preferably 1.0 to 2.0 times, more preferably 1.01 to 1.5 times. The final stretch ratio in the width direction is preferably 1.01 to 2.5 times, more preferably 1.05 to 2.0 times.
[0346] There are no particular restrictions on the method of stretching the film. For example, as a stretching method, there can be cited a method of imparting a peripheral speed difference to a plurality of rollers, and utilizing the peripheral speed difference between the rollers to stretch the film in the longitudinal direction. As a stretching method, there can be cited a method of fixing both ends of the film with cloth clips or needle plates, and extending the interval between the cloth clips or needle plates in the conveying direction to stretch the film in the longitudinal direction. Similarly, there can be cited a method of extending the interval between the cloth clips or needle plates in the width direction to stretch the film in the transverse direction. Similarly, there can be cited a method of extending the interval between the cloth clips or needle plates in both the conveying direction and the width direction to stretch the film in both the longitudinal and transverse directions.
[0347] These stretching methods may be used in combination. In addition, in the case of the tenter method, if the clip portion is driven by a linear drive method, stretching can be performed smoothly, reducing the risk of film breakage, etc.
[0348] The stretching while maintaining the width or the transverse direction is preferably performed by a tentering method, which may be a pin tentering machine or a clip tentering machine.
[0349] The fast axis or slow axis of the film exists in the film surface. If the angle with the conveying direction is set to θ1, θ1 is preferably in the range of -0.5 to +0.5°, more preferably in the range of -0.3 to +0.3°, and further preferably in the range of -0.2 to +0.2°. This θ1 can be defined as an orientation angle. θ1 can be measured using an automatic birefringent meter "KOBRA-21ADH" (Prince Measuring Instruments). By making θ1 within the above range, high brightness can be obtained in the displayed image. In addition, light leakage can be suppressed or prevented, and colors can be faithfully reproduced in a color liquid crystal display device.
[0350] (4.6) Step of further drying the film
[0351] In the process of further drying the film, the peeled film is further dried. Drying can be performed after stretching or simultaneously. The residual solvent content of the dried film is preferably 1% by mass or less, more preferably 0.1% by mass or less, and further preferably 0.01% by mass or less.
[0352] The drying method is not particularly limited, and examples thereof include a roll drying method in which the film is dried by passing through a plurality of rolls alternately arranged vertically. Alternatively, the film may be dried while being stretched using the tenter method described above.
[0353] The method of drying the film is not particularly limited, and examples thereof include hot air, infrared rays, heating rolls, microwaves, etc. From the viewpoint of simplicity, the drying method is preferably hot air.
[0354] The drying temperature is preferably increased stepwise within a range of 40 to 200° C. From the viewpoint of dimensional stability, the drying temperature is more preferably within a range of 50 to 140° C.
[0355] (4.7) Step of winding the finished film
[0356] The finished film is preferably stored by being wound into a roll, for example.
[0357] (5) Physical properties of the second optical film
[0358] (5.1) Delay value
[0359] The retardation value Ro is preferably in the range of 30 to 90 nm. The retardation value Rth is preferably in the range of 100 to 200 nm. By setting the retardation value in the above range, light leakage when the liquid crystal display device having the polarizing plate of the present invention is observed from an oblique direction can be suppressed.
[0360] (5.2) Thickness
[0361] The thickness of the film is preferably within a range of 10 to 200 μm, more preferably within a range of 10 to 60 μm, and even more preferably within a range of 10 to 40 μm.
[0362] (5.3) Width
[0363] The width of the film is preferably in the range of 1 to 4 m, more preferably in the range of 1.3 to 4 m, and further preferably in the range of 2.2 to 3.0 m. By setting the width in the range of 2.2 to 3.0 m, both uniformity of stretching and productivity can be achieved at a high level.
[0364] 4. Polarizer
[0365] In the present invention, "polarizer" refers to an element that allows only light of a certain polarization plane to pass through, and a layer including the element. As a polarizer, for example, a polyvinyl alcohol-based polarizing film can be cited. Among the polyvinyl alcohol-based polarizing films, one is formed by dyeing the polyvinyl alcohol-based film with iodine and one is formed by dyeing the polyvinyl alcohol-based film with a dichroic dye.
[0366] The method for producing the polarizer includes forming a film from a polyvinyl alcohol aqueous solution, uniaxially stretching the obtained film, and then dyeing it. Alternatively, the film may be uniaxially stretched after dyeing and subjected to durability treatment with a boron compound or the like.
[0367] The thickness of the polarizer is preferably in the range of 2 to 30 μm, more preferably in the range of 2 to 20 μm.
[0368] As polyvinyl alcohol, ethylene-modified polyvinyl alcohol described in Japanese Patent Publication No. 2003-248123, Japanese Patent Publication No. 2003-342322, etc. can be cited. The content of ethylene units in the ethylene-modified polyvinyl alcohol is in the range of 1 to 4 mol%, the degree of polymerization is in the range of 2000 to 4000, and the degree of saponification is in the range of 99.0 to 99.99 mol%. Among them, ethylene-modified polyvinyl alcohol having a hot water cut-off temperature in the range of 66 to 73° C. is preferred. The polarizing film of the ethylene-modified polyvinyl alcohol has excellent polarization performance and durability, less color unevenness, and is particularly preferably used in large liquid crystal display devices.
[0369] 5. Manufacturing method of polarizing film
[0370] The polaroid of the present invention can be made by a conventional method. The surface side of the first protective film involved in the present invention that is opposite to the polarizer is appropriately surface treated, and it is bonded to at least one side of the polarizer that is made by immersion stretching in an iodine solution using an ultraviolet curing adhesive or an aqueous adhesive described later. The second protective film is also bonded to the other side of the polarizer in the same manner.
[0371] As for the direction of bonding with the polarizer, for example, a method of bonding so that the absorption axis of the polarizer and the slow axis of each protective film are perpendicular to each other is preferably used.
[0372] (1) UV curing adhesive
[0373] The polarizing plate of the present invention is preferably produced by bonding the optical film and the polarizer with an ultraviolet curing adhesive. By using an ultraviolet curing adhesive, a polarizing plate having high strength and excellent flatness can be obtained even if it is thin.
[0374] (1.1) Composition of UV-curable adhesive
[0375] As the ultraviolet curable adhesive composition for polarizer, there can be mentioned a photo-radical polymerizable composition using photo-radical polymerization and a photo-cationic polymerizable composition using photo-cationic polymerization. In addition, as the ultraviolet curable adhesive composition for polarizer, there can be mentioned a mixed composition using photo-radical polymerization and photo-cationic polymerization.
[0376] Examples of the photoradical polymerizable composition include the composition described in Japanese Patent Application Laid-Open No. 2008-009329, which contains a radical polymerizable compound containing a polar group such as a hydroxyl group or a carboxyl group and a radical polymerizable compound containing no polar group at a specific ratio.
[0377] The radical polymerizable compound contained in the photo-radical polymerizable composition is preferably a compound having an ethylenically unsaturated bond that can be subjected to radical polymerization. Examples of the compound having an ethylenically unsaturated bond that can be subjected to radical polymerization include compounds having a (meth)acryloyl group. Examples of the compound having a (meth)acryloyl group include N-substituted (meth)acrylamide compounds, (meth)acrylate compounds, and the like.
[0378] In addition, (meth)acryloyl means an acryloyl group or a methacryloyl group, (meth)acrylate means an acrylate or a methacrylate, and (meth)acrylamide means an acrylamide or a methacrylamide.
[0379] Examples of the photocationic polymerization composition include the composition described in Japanese Patent Application Laid-Open No. 2011-028234, which contains (α) a cationically polymerizable compound, (β) a photocationic polymerization initiator, (γ) a photosensitizer that exhibits maximum absorption for light having a wavelength longer than 380 nm, and (δ) a naphthalene-based photosensitizer.
[0380] Examples of the cationically polymerizable compound include epoxy compounds and oxetane compounds.
[0381] The ultraviolet curing adhesive is not limited to these, and known ones can be used.
[0382] (2) Method for manufacturing polarizing plate
[0383] After pre-treating the optical film and the polarizer, a UV curable adhesive is applied, and then the optical film and the polarizer are bonded together using the UV curable adhesive. Then, the UV curable adhesive is cured.
[0384] (2.1) Pre-treatment process
[0385] In the pretreatment step, the adhesion-facilitating treatment is performed on the adhesion surface of the optical film and the polarizer. Examples of the adhesion-facilitating treatment include corona treatment and plasma treatment.
[0386] (2.2) Coating process
[0387] In the coating process, the above-mentioned ultraviolet curing adhesive is applied to at least one of the bonding surfaces of the optical film and the polarizer. When the ultraviolet curing adhesive is directly applied to the surface of the optical film or the polarizer, the coating method is not limited. As the coating method, for example, a scraper, a winding rod, a die coater, a comma coater, a gravure coater, etc. can be cited, and various wet coating methods can be used. In addition, after the ultraviolet curing adhesive is applied between the optical film and the polarizer, a roller or the like can be used to pressurize the ultraviolet curing adhesive so that the ultraviolet curing adhesive is evenly spread.
[0388] (2.3) Lamination process
[0389] In the laminating process, when the ultraviolet curing adhesive is applied to the surface of the polarizer in the previous coating process, the optical film is overlapped on the ultraviolet curing adhesive. When the ultraviolet curing adhesive is applied to the surface of the optical film, the polarizer is overlapped on the ultraviolet curing adhesive.
[0390] When the ultraviolet curing adhesive is cast between the optical film and the polarizer, the optical film and the polarizer are overlapped in this state. Usually, in this state, the optical film side of both sides is clamped with a pressure roller or the like and pressurized. As the material of the pressure roller, for example, metal, rubber, etc. can be cited. The pressure rollers arranged on both sides can be made of the same material or different materials.
[0391] (2.4) Curing process
[0392] In the curing step, ultraviolet rays are irradiated to the applied ultraviolet curing adhesive. Then, the ultraviolet curing adhesive is cured, and the overlapped optical film is bonded to the polarizer via the ultraviolet curing adhesive. In the present invention, the light-transmitting optical film is overlapped on both sides of the polarizer via the ultraviolet curing adhesive. Preferably, ultraviolet rays are irradiated in this state to cure the ultraviolet curing adhesives on both sides simultaneously.
[0393] The conditions for irradiation with ultraviolet rays are not particularly limited as long as they are conditions that can cure the ultraviolet curing adhesive. The irradiation amount of ultraviolet rays is preferably 50 to 1500 mJ / cm 2 The range of is preferably 100 to 500 mJ / cm 2 In the present invention, from the viewpoint of improving the yield, it is preferred to irradiate ultraviolet rays from the second optical film side.
[0394] When a continuous production line is used to manufacture a polarizer, the production line speed is preferably within the range of 1 to 500 m / min, more preferably within the range of 5 to 300 m / min, and further preferably within the range of 10 to 100 m / min. By making the production line speed above 1 m / min, productivity can be ensured. In addition, damage to the optical film can be suppressed to obtain a polarizer with excellent durability. By making the production line speed below 500 m / min, the ultraviolet curing adhesive can be fully cured. An adhesive layer with a target hardness and excellent adhesion can be formed. It should be noted that the production line speed is preferably adjusted in consideration of the curing time of the adhesive.
[0395] 6. Display device
[0396] The display device of the present invention is characterized in that it includes the polarizing plate, and the second optical film is disposed on the liquid crystal cell side. By including the polarizing plate, color unevenness and contrast fluctuation caused by water inclusion can be suppressed.
[0397] The polarizing plate of the present invention can be used in liquid crystal display devices of various drive modes such as STN, TN, OCB, HAN, VA (MVA, PVA), IPS, OCB, etc. Among them, it is preferably used in IPS type liquid crystal display devices.
[0398] Liquid crystal display devices usually use two polarizers, a polarizer on the visible side and a polarizer on the backlight side. The polarizer of the present invention can be used as a polarizer on both sides or as a polarizer on one side. The direction of lamination of the polarizer in the IPS type liquid crystal display device can be referred to, for example, Japanese Patent Publication No. 2005-234431.
[0399] The liquid crystal cell according to the present invention comprises a liquid crystal layer and a pair of substrates sandwiching the liquid crystal layer. From the viewpoint of reducing the thickness and weight of the display device, the pair of substrates are preferably glass substrates with a thickness in the range of 0.3 to 0.7 mm.
[0400] Figure 2 This is a schematic cross-sectional view showing an example of the configuration of a display device (100) in which polarizing plates (101A and 101B) of the present invention are arranged on both surfaces of a liquid crystal cell (101C).
[0401] Figure 2 In the invention, a liquid crystal unit (101C) is formed by sandwiching two surfaces of a liquid crystal layer (107) with glass substrates (108A and 108B) as transparent substrates. Polarizers (101A and 101B) are arranged on the surfaces of the glass substrates (108A and 108B) via an adhesive layer (106) to form a display device (100).
[0402] In the polarizing plates (101A and 101B), the first optical film is bonded to positions 102A and 102B, and the second optical film is bonded to positions 105A and 105B. The optical films are bonded to the polarizers (104A and 104B) using ultraviolet curing adhesives (103A to 103D).
[0403] The liquid crystal unit (101C) has an alignment film, a transparent electrode and glass substrates (108A and 108B) on both sides of the liquid crystal material. As the material of the glass substrate, for example, soda lime glass, silicate glass, etc. can be cited. Among them, silicate glass is preferred, and specifically, silica glass or borosilicate glass is more preferred.
[0404] The glass constituting the glass substrate is preferably an alkali-free glass substantially free of alkali components. Specifically, the content of alkali components in the glass substrate is preferably 1000 ppm or less. The content of alkali components in the glass substrate is more preferably 500 ppm or less, and still more preferably 300 ppm or less. By using an alkali-free glass substantially free of alkali components, it is possible to suppress the soda blowing caused by the substitution of cations on the surface of the optical film. As a result, it is possible to suppress the decrease in the density of the surface of the optical film and prevent the breakage of the glass substrate.
[0405] The glass substrate can be produced by a known method, such as the float method, the down-draw method, the overflow down-draw method, etc. Among them, from the perspective that the surface of the glass substrate does not come into contact with the forming member during forming and does not cause damage to the surface of the obtained glass substrate, the overflow down-draw method is preferred.
[0406] The glass substrate can be a commercially available product. As commercially available glass substrates, for example, "AN100" (thickness 500 μm, manufactured by Asahi Glass Co., Ltd.), "EAGLE XG(r)Slim" (thickness 300 μm, 400 μm, etc., manufactured by CORNING Incorporated), glass substrates (in the range of 100 - 200 μm in thickness, manufactured by Nippon Electric Glass Co., Ltd.) can be cited.
[0407] As Figure 2 shown, the polarizers (101A, 101B) and the liquid crystal cell (101C) are bonded via an adhesive layer (106). As the adhesive layer, a layer formed by using a double-sided tape, an ultraviolet curable adhesive, etc. can be cited. As the double-sided tape, for example, a tape without a substrate "MO-3005C" (thickness 25 μm, manufactured by LINTEC Corporation) can be cited. The bonding method is not particularly limited, and a known method can be used.
[0408] In addition to the effects of the present invention, the liquid crystal display device of the present invention has excellent interlayer adhesion, excellent lightfastness, egg unevenness resistance of the displayed image, etc. By using the polarizer of the present invention, especially even for a large screen of 30 inches or more, a liquid crystal display device with excellent visibility, thin film and light weight can be obtained.
[0409] Examples
[0410] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to these examples. It should be noted that in the examples, the expressions "parts" or "%" indicate "parts by mass" or "% by mass" unless otherwise specified.
[0411] In addition, in the following examples, unless otherwise specified, the operations are carried out at room temperature (25 °C).
[0412] 1. Production of polarizer
[0413] (1) Preparation of the first optical film
[0414] The first optical films (Optical Films Nos. 1 and 2) were produced by the following method.
[0415] (1.1) Preparation of optical film 1
[0416] (1.1.1) Synthesis of Polyester A
[0417] The temperature of the esterification reaction tank was raised, and when the temperature reached 200°C, the following components were added.
[0418] Terephthalic acid 86.400 parts by mass
[0419] Ethylene glycol 64.600 parts by mass
[0420] While the mixture was stirred, the following catalyst was added to the esterification reaction tank, and then a pressure esterification reaction was carried out under the conditions of a gauge pressure of 0.34 MPa and a temperature of 240°C.
[0421] Antimony trioxide 0.017 parts by mass
[0422] Magnesium acetate tetrahydrate 0.064 parts by mass
[0423] Triethylamine 0.160 parts by mass
[0424] Next, the esterification reaction tank was returned to normal pressure, and the following components were added.
[0425] Phosphoric acid 0.014 parts by mass
[0426] The temperature of the reactant was further increased to 260° C. over 15 minutes, and the following components were added to the esterification reaction tank.
[0427] Trimethyl phosphate 0.012 parts by mass
[0428] After 15 minutes, the reactants were dispersed using a high-pressure disperser, and after another 15 minutes, the reactants were transferred to a polycondensation reaction tank and subjected to a polycondensation reaction at 280° C. under reduced pressure.
[0429] After the polycondensation reaction is completed, the reaction product is filtered using "NASLON (registered trademark) FILTER NF-05S" (95% cutoff particle size: 5 μm, manufactured by Nippon Seisen Co., Ltd.). The reaction product is extruded from a nozzle into a bundle. Then, the reaction product is cooled and solidified using cooling water that has been previously filtered (pore size: less than 1 μm), and cut into particles. The intrinsic viscosity of the obtained polyester A (polyethylene terephthalate: PET) is 0.62 dL / g. In addition, the polyester does not substantially contain inactive particles and internal precipitated particles.
[0430] (1.1.2) Preparation of polyester B
[0431] The dried ultraviolet absorber and the polyester A were mixed at the following ratio and mixed using a kneading extruder to obtain a polyester B containing an ultraviolet absorber.
[0432] UV absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzo Oxazin-4-one)
[0433] 10 parts by mass
[0434] Polyester A 90 parts by mass
[0435] (1.1.3) Preparation of Adhesion-Modified Coating Liquid
[0436] The following components are used to carry out transesterification and polycondensation reactions by a known method to prepare a water-dispersible sulfonic acid metal salt group-containing copolyester resin.
[0437] The dicarboxylic acid component is blended in the following ratios relative to the entire dicarboxylic acid component.
[0438] Terephthalic acid 46 mol%
[0439] Isophthalic acid 46 mol%
[0440] Sodium 5-sulfoisophthalate 8 mol%
[0441] The diol component is blended in the following ratios relative to the entire diol component.
[0442] Ethylene glycol 50 mol%
[0443] Neopentyl glycol 50 mol%
[0444] Next, mix the following ingredients.
[0445]
[0446]
[0447] The mixture was then heated and stirred, and the following components were added when the temperature reached 77° C. Stirring was continued until no resin lumps were formed, and the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolyester resin solution having a solid content concentration of 5.0% by mass.
[0448] 5.00 parts by mass of the above-mentioned copolyester resin
[0449] The following components were dispersed to prepare an aqueous dispersion of silica particles.
[0450] Agglomerated silica particles "Sylysia 310" (manufactured by Fuji Silysia Co., Ltd.) 3.00 parts by mass
[0452] Water 50.00 parts by mass
[0453] Mix the following ingredients.
[0454] 99.46 parts by mass of the above water-dispersible copolyester resin solution
[0455] 0.54 parts by mass of aqueous dispersion of silica particles
[0456] While the mixture was stirred, the following components were added to obtain an adhesion-improving coating liquid.
[0457] Water 20.00 parts by mass
[0458] (1.1.4) Formation of Optical Film 1
[0459] The following polyester pellets were dried under reduced pressure at 135°C and 133.3 Pa (1 Torr) for 6 hours, and then supplied to extruder 2 (for intermediate layer II). Thereafter, the pellets were melted at 285°C.
[0460] Polyester A 90 parts by mass
[0461] Polyester B 10 parts by mass
[0462] The synthesized polyester A was dried by a conventional method and then supplied to an extruder 1 (for outer layer I and outer layer III) to be melted at 285°C.
[0463] The molten polyesters are filtered using a filter material of a stainless steel sintered body (removing 95% of the rated filtration accuracy of 10 μm particles). Then, two types of three-layer confluence blocks are stacked and extruded from the die head into sheets. Thereafter, the extruded polyester is wound on a casting drum with a surface temperature of 30°C for cooling and solidification using an external electrostatic casting method. Then, an unstretched polyester film (PET film) is obtained. It should be noted that the discharge volume of each extruder is adjusted in such a way that the thickness ratio of layer I, layer II, and layer III becomes 10:80:10.
[0464] Next, the unstretched polyester film was coated with a reverse roll method on both sides thereof so that the coating amount after drying was 0.08 g / m 2 The adhesiveness-modified coating liquid was applied in a manner of . Thereafter, the coating liquid was dried at 80° C. for 20 seconds.
[0465] The unstretched polyester film was introduced into a tenter stretching machine, and the film was stretched to 4.0 times in the width direction in a hot air zone at a temperature of 125°C while holding the film ends with a cloth clip. Next, the film was treated at a temperature of 225°C for 30 seconds while maintaining the film's stretched width in the width direction. The film was further subjected to a 3% relaxation treatment in the width direction. Then, a uniaxially oriented optical film 1 having a thickness of 50 μm was obtained.
[0466] (1.2) Preparation of optical film 2
[0467] Optical Film 2 was obtained in the same manner as in the preparation of Optical Film 1 except that triacetyl cellulose (TAC) was used instead of polyester.
[0468] (2) Preparation of the Second Optical Film
[0469] The second optical films (optical films Nos. 3 to 17) were produced according to the following method.
[0470] (2.1) Preparation of optical film 3
[0471] First, the details of cellulose acetate and polyester additives used in the preparation of the second optical film are shown below.
[0472] (Cellulose acetate)
[0473] Cellulose acetate 1 (AC1): acetyl substitution degree 2.50
[0474] Cellulose acetate 2 (AC2): acetyl substitution degree 2.20
[0475] Cellulose acetate 3 (AC3): acetyl substitution degree 2.40
[0476] Cellulose acetate 4 (AC4): acetyl substitution degree 2.60
[0477] Cellulose acetate 5 (AC5): acetyl substitution degree 2.70
[0478] Cellulose acetate 6 (AC6): acetyl substitution degree 2.90
[0479] (additive)
[0480] The structural formula of the additive is shown below.
[0481] The n value of compounds P11 and P21 is 1, and the n value of compounds P12 and P22 is 2.
[0482] Compound P11 (n=1) and Compound P12 (n=2)
[0483]
[0484] Compound P21 (n=1) and Compound P22 (n=2)
[0485]
[0486] Compound P31
[0487]
[0488] (2.1.1) Synthesis of additives
[0489] (2.1.1.1) Synthesis of compound P11
[0490] The reaction formula for synthesizing compound P11 from terephthaloyl chloride is shown below.
[0491]
[0492] (Synthesis of Intermediate 1)
[0493] The following ingredients were dissolved in ethyl acetate.
[0494] Propylene glycol 228.0 parts by mass
[0495] 121.0 parts by mass of triethylamine
[0496] The following components were added while maintaining the temperature of the reaction solution at 50°C or lower.
[0497] Terephthaloyl chloride 101.5 parts by mass
[0498] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution and stirred, and the aqueous layer was removed. The organic layer was further washed with water 4 times. The solvent of the organic layer was distilled off under reduced pressure to obtain 127 parts by mass of Intermediate 1 (yield 90%).
[0499] (Synthesis of Compound P11)
[0500] The following ingredients were dissolved in toluene.
[0501] Intermediate 1 71.5 parts by mass
[0502] 30.0 parts by mass of triethylamine
[0503] The following components were added while maintaining the temperature of the reaction solution at 50°C or lower.
[0504] 19.3 parts by mass of p-toluoyl chloride
[0505] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution and stirred, and the aqueous layer was removed. The organic layer was further washed twice with a 5% sodium carbonate aqueous solution. After washing the organic layer with saturated brine, it was concentrated under reduced pressure. The obtained residue was purified by silica gel column chromatography to obtain 37.5 parts by mass of compound P11 (yield 75%).
[0506] (2.1.1.2) Synthesis of compound P21
[0507] In the synthesis of compound P11, compound P21 was obtained in the same manner except that the amount of p-toluoyl chloride added was changed to 38.6 parts by mass.
[0508] (2.1.1.3) Synthesis of compound P31
[0509] The following ingredients were dissolved in ethyl acetate.
[0510] Propylene glycol 228.0 parts by mass
[0511] 121.0 parts by mass of triethylamine
[0512] The following components were added while maintaining the temperature of the reaction solution at 50°C or lower.
[0513] 19.3 parts by mass of p-toluoyl chloride
[0514] After the addition was completed, the reaction solution was stirred at room temperature for 5 hours. Water was added to the reaction solution and stirred, and the aqueous layer was removed. The organic layer was further washed with water 4 times. The solvent of the organic layer was distilled off under reduced pressure to obtain compound P31 (yield 90%).
[0515] (2.1.2) Preparation of coating
[0516] 〈Microparticle dispersion〉
[0517] The following components were stirred and mixed in a disperser for 50 minutes and then dispersed in a Monton colloid mill to obtain a fine particle dispersion.
[0518] Microparticles "Aerosil (registered trademark) R812" (manufactured by Nippon Aerosil Co., Ltd.)
[0519] 11.0 parts by mass
[0520] Ethanol 89.0 parts by mass
[0521] 〈Microparticle Additive Liquid〉
[0522] Cellulose acetate having a degree of substitution of 2.40 is added to a dissolving tank filled with dichloromethane and heated to completely dissolve. Thereafter, the solution is filtered using "Anzai Filter Paper No. 244" (manufactured by Anzai Filter Paper Co., Ltd.). The above-mentioned microparticle dispersion is slowly added thereto while the filtered cellulose acetate solution is fully stirred. Then, the mixed solution is dispersed using a grinder in such a manner that the particle size of the secondary particles becomes a predetermined size. The obtained dispersion is filtered using "Finemet NF" (manufactured by Nippon Seisen Co., Ltd.) to prepare a microparticle addition solution.
[0523] Dichloromethane 99.0 parts by mass
[0524] Cellulose acetate 4.0 parts by mass
[0525] Microparticle dispersion 11.0 parts by mass
[0526] Next, a main coating liquid having the following composition was prepared.
[0527] First, add dichloromethane and ethanol to a pressure dissolving tank. Add cellulose acetate with a degree of substitution of 2.40 into the pressure dissolving tank filled with the solvent while stirring. Heat it and completely dissolve it under stirring. Further add two additives to the solution and dissolve them. Filter the solution using "Anzai Filter Paper No. 244" (manufactured by Anzai Filter Paper Co., Ltd.) to prepare the main coating liquid.
[0528] 〈Main coating liquid composition〉
[0529]
[0530] 2 parts by mass of the fine particle additive liquid were added to 100.0 parts by mass of the main coating liquid, and the mixture was mixed thoroughly with an inline mixer (Toray static line mixer) "Hi-Mixer SWJ" (manufactured by Toray Engineering Co., Ltd.) to prepare a coating. The content of compound P11 in the coating was 5% by mass relative to the mass of cellulose acetate. Similarly, the content of compound P21 was 5% by mass relative to the mass of cellulose acetate.
[0531] (2.1.3) Formation of Optical Film 3
[0532] The prepared coating was uniformly cast on a stainless steel belt at a temperature of 22°C and a width of 2 m using a belt casting device. On the stainless steel belt, the solvent in the wet film was evaporated until the residual solvent content was less than 100%. Then, the film was peeled off from the stainless steel belt at a peeling tension of 160 N / m.
[0533] Next, the peeled film was sheared by evaporating the solvent at 35° C. Thereafter, the film was stretched to 1.6 times the original width in the width direction (TD direction) at a temperature of 160° C. using a tenter stretching machine. The residual solvent content of the film at the start of the stretching using the tenter was 3 to 15% by mass.
[0534] Thereafter, the film was dried while being conveyed by a plurality of rollers in a drying zone at 120° C. and 140° C. The film was cut into a width of 2.5 m, and knurling with a width of 10 mm and a height of 2.5 μm was performed on both ends of the film. Thereafter, the film was wound around a mandrel to obtain an optical film 3 with a thickness of 40 μm and a winding length of 3900 m.
[0535] (2.2) Preparation of Optical Films 4 to 17
[0536] Optical films 4 to 17 were obtained in the same manner except that the type of resin and the type and content of additives in the preparation of optical film 3 were changed as shown in Table I. The thickness of optical films 4 to 17 was 40 μm.
[0537] (3) Preparation of polarizer
[0538] Prepare a long polyvinyl alcohol film with a thickness of 60 μm. While the film is continuously conveyed via a guide roller, the film is immersed in a dyeing bath (30°C) containing iodine and potassium iodide for dyeing, and the film is stretched 2.5 times. Thereafter, the film is stretched and cross-linked for a total of 5 times in an acidic bath (60°C) to which boric acid and potassium iodide are added. The obtained iodine-PVA polarizer film with a thickness of 12 μm is dried in a dryer at 50°C for 30 minutes. Then, a polarizer with a moisture content of 4.9% is obtained.
[0539] (4) Preparation of polarizer
[0540] (4.1) Preparation of polarizer 1
[0541] The optical film 1 (first optical film), the optical film 3 (second optical film), and a polarizer are bonded together to produce a polarizing plate 1 .
[0542] (4.1.1) Preparation of water-based adhesive
[0543] The following components were mixed to prepare a water-based adhesive.
[0544] Pure water 100.0 parts by mass
[0545] Carboxyl-modified polyvinyl alcohol "Kuraray Poval (registered trademark) KL318" (manufactured by KURARAY CORPORATION) 3.0 parts by mass
[0546] Water-soluble polyamide epoxy resin "Sumirez (registered trademark) Resin 650" (30% solid content concentration aqueous solution, manufactured by SUMIKA CHEMTEX Co., Ltd.) 1.5 parts by mass
[0547] (4.1.2) Pretreatment of the second optical film
[0548] The optical film 3 was immersed in a saponification treatment solution (aqueous sodium hydroxide solution at 60°C, concentration 10% by mass) for 30 seconds. Next, the optical film 3 was immersed in a water bath for 5 seconds. This operation was performed twice. Thereafter, the optical film 3 was cleaned by spraying water for 5 seconds and then dried. The drying conditions were 70°C and 2 minutes.
[0549] Next, the optical film 3 was immersed in water at 30° C. for 10 seconds to perform swelling treatment. Thereafter, the optical film 3 was dried at 40° C. for 53 seconds.
[0550] (4.1.3) Lamination of optical film and polarizer
[0551] The surfaces of the optical film 1 and the optical film 3 to be bonded to the polarizer were subjected to corona treatment. Thereafter, the above-mentioned water-based adhesive was applied to the bonding surfaces to the polarizer, and the optical films were bonded to both sides of the polarizer. Thereafter, the bonded laminate was immediately dried for 5 minutes in a hot air circulation dryer set at 80° C., thereby obtaining a polarizing plate 1.
[0552] (4.2) Preparation of polarizing plates 2 to 16
[0553] In the preparation of the polarizing plate 1, polarizing plates 2 to 16 were obtained in the same manner except that the types of the first and second optical films were changed as shown in Tables I and II.
[0554] Table I and Table II show the structures of the obtained polarizing plates.
[0555] In addition, "-" in Table II means that the component is not contained. The "substitution degree" in the table means the acetyl substitution degree.
[0556] The content of each additive in Table II represents the ratio of the additive to the mass of cellulose acetate. Therefore, for example, in the case of Example 2, if converted to the ratio relative to the total mass of polyester (I) and polyester (II), the content of polyester (II) is 80% by mass.
[0557] [Table 1]
[0558] Table I
[0559]
[0560] [Table 2]
[0561] Table II
[0562]
[0563] 2. Evaluation
[0564] (Manufacturing of Liquid Crystal Display Device)
[0565] Liquid crystal display devices 1 to 16 were produced by the following method using the polarizing plates 1 to 16 produced above. The obtained liquid crystal display devices were evaluated for fluctuation in in-plane contrast and water resistance (color unevenness due to water inclusion).
[0566] An IPS liquid crystal cell having two glass substrates with a thickness of 0.5 mm and a liquid crystal layer disposed therebetween was prepared. Then, the polarizers 1 to 16 prepared above were bonded together through an adhesive layer in such a manner that the second optical film became the liquid crystal cell side, thereby obtaining liquid crystal display devices 1 to 16. The polarizers ( Figure 2 The absorption axis of the polarizer (101A) described in the figure is the same as that of the polarizer on the backlight side ( Figure 2 101B) described in the method is carried out in a manner where the absorption axes of the polarizers are orthogonal.
[0567] (1) Color unevenness caused by water content (water resistance)
[0568] The obtained liquid crystal display device is placed flat on a table or the like. "BEMCOT (registered trademark)" (manufactured by ASAHI KASEI Co., Ltd.) is placed on a part of the liquid crystal display device so that BEMCOT (registered trademark) contains water. In order to prevent BEMCOT (registered trademark) from drying, BEMCOT (registered trademark) is covered with a polyester (PET) film having a thickness of 100 μm.
[0569] A signal to display black was input from the PC to the liquid crystal display device, and the power of the liquid crystal display device was turned on and left for 24 hours. The room temperature was set to 23°C and the panel temperature was set to 38°C. After 24 hours, the BEMCOT (registered trademark) was removed. One minute later, the LCD portion of the liquid crystal display device where the BEMCOT (registered trademark) was present was * L as the water-immersed part * The brightness was measured using an image colorimeter "EZContrast" (manufactured by ELDIM). In addition, the L values of the portion of the liquid crystal display device without BEMCOT (registered trademark) were measured. * L as the non-impregnated part * , measured with EZContrast. Then, L is calculated from the following formula: * Rate of change.
[0570] L * Change rate = (L *) / (L of non-impregnated part * )
[0571] The measurement using EZContrast was performed in a color mode with the liquid crystal display device displaying black. The conditions for water immersion were: the liquid crystal display device was powered on and left to stand for 24 hours with a BEMCOT (registered trademark) attached that fully permeated water.
[0572] L * In L * a * b * Represents brightness in color space.
[0573] The following criteria were used to evaluate L * Rate of change: There is no problem in practical use if B or more (A and B) is used.
[0574] AA:L * The rate of change is less than 1.05.
[0575] A: L * The rate of change is greater than 1.05 and less than or equal to 1.30.
[0576] B:L * The rate of change is greater than 1.30 and less than or equal to 1.55.
[0577] C:L * The rate of change is greater than 1.55.
[0578] It should be noted that in the evaluations AA and A, no difference between the water-immersed area and the non-immersed area was observed. * In evaluation B, the color unevenness caused by the change of L in the water-immersed area and the non-immersed area was slightly observed. * In evaluation C, the water-immersed area and the non-immersed area were observed to have uneven color. * The uneven color caused by the change is a practical problem. * When the variation ratio is greater than 1.80, severe color unevenness is observed.
[0579] (2) Fluctuation of contrast
[0580] The backlight of the obtained liquid crystal display device was continuously turned on for 1 hour under an environment of 23° C. and 55% RH, and then the front contrast ratio was measured. The front contrast ratio was measured according to the following procedure.
[0581] i) The front brightness of the display screen when the liquid crystal display device displays white is measured using "EZ-Contrast 160D" (manufactured by ELDIM). Here, "front brightness" refers to the brightness measured from the normal direction of the display screen. The front brightness of the display screen when the liquid crystal display device displays black is measured in the same way.
[0582] ii) The ratio of the front brightness of the display screen when white is displayed to the front brightness of the display screen when black is displayed is defined as the front contrast ratio.
[0583] Front contrast = (front brightness when displaying white) / (front brightness when displaying black)
[0584] In the display screen of the liquid crystal display device, the front contrast ratio of 9 points is measured. Figure 3 As shown, the 9 points in the display screen are the center point of the display device and the other 8 points. 4 of the other 8 points are points on the diagonal lines of the display device. The distance from the four corners (A to D) of the display device to each point is 1 / 10 of the length of the diagonal line. In addition, the remaining 4 points are points on the lines that divide the display device into two equal parts vertically and horizontally, and these bisectors are lines passing through the midpoints (E to H) of the four sides of the display device. The distance from the midpoints (E to H) of the four sides of the display device to each point is 1 / 10 of the length of the bisector.
[0585] The average value of the obtained 9-point front contrast is calculated. Also, among the obtained 9-point front contrast, the maximum value of the front contrast having the largest difference from the average value is calculated. Then, the fluctuation [%] of the front contrast is calculated by the following formula.
[0586] Fluctuation of front contrast [%]
[0587] ={(maximum value of front contrast)-(average value of front contrast)} / (average value of front contrast)×100
[0588] The fluctuation of the front contrast was evaluated according to the following criteria: B or higher (AA to B) was considered to have no practical problem.
[0589] AA: Fluctuation in front contrast is less than 1%.
[0590] A: The fluctuation of the front contrast is 1% or more and less than 5%.
[0591] B: The fluctuation of the front contrast is 5% or more and less than 10%.
[0592] C: Fluctuation in front contrast is 10% or more.
[0593] In the evaluation AA, no unevenness due to the fluctuation of the front contrast was observed. In the evaluation A, slight unevenness due to the fluctuation of the front contrast was observed, but there was no problem in practical use. In the evaluation B, unevenness due to the fluctuation of the front contrast was slightly observed, but there was no problem in practical use. In the evaluation C, obvious unevenness due to the fluctuation of the front contrast was observed, which was a problem in practical use.
[0594] The evaluation results are shown in Table III.
[0595] It should be noted that "-" in the table means that light leakage occurred and measurement could not be performed.
[0596] [Table 3]
[0597] Table III
[0598]
[0599] It is clear from the Examples and Comparative Examples that the polarizing plate of the present invention can suppress color unevenness and contrast fluctuation caused by water inclusion, and improve the visibility of a display device.
[0600] From Examples 1, 2, 11 and 12, it is understood that color unevenness can be further suppressed by setting the content of the polyester (II) to 70 to 90% by mass based on the total mass of the polyester (I) and the polyester (II).
[0601] From Examples 1 and 3, it is understood that color unevenness can be further suppressed by further containing polyester (III).
[0602] From Examples 1 and 8 to 10, it is understood that by setting the width of the second optical film to be within the range of 2.2 to 3.0 m, the contrast fluctuation can be further suppressed.
Claims
1. A polarizing plate, characterized in that A polarizing plate comprising a first optical film, a polarizer and a second optical film in this order, The first optical film contains polyester, The second optical film contains a polyester represented by the following general formula (I), a polyester represented by the following general formula (II), and cellulose acetate having a degree of substitution of acetyl groups in the range of 2.30 to 2.
80. General formula (I): T-(DP) n -D General formula (II): T-(DP) n -DT In the general formulae (I) and (II), T represents a phenylcarboxylic acid residue, D represents an alkylene glycol residue having 2 to 12 carbon atoms, an arylene glycol residue having 6 to 12 carbon atoms, or an oxyalkylene glycol residue having 4 to 12 carbon atoms, P represents an alkylene dicarboxylic acid residue having 4 to 12 carbon atoms or an arylene dicarboxylic acid residue having 6 to 12 carbon atoms, n represents an integer of 1 or greater.
2. The polarizing plate according to claim 1, characterized in that The content of the polyester represented by the general formula (II) is in the range of 70 to 90% by mass relative to the total mass of the polyester represented by the general formula (I) and the polyester represented by the general formula (II).
3. The polarizing plate according to claim 1, characterized in that The polyester contained in the first optical film is polyethylene terephthalate.
4. The polarizing plate according to claim 1, characterized in that The second optical film further contains an ester represented by the following general formula (III): General formula (III): TD.
5. The polarizing plate according to claim 1, characterized in that The width of the second optical film is in the range of 2.2 to 3.0 m.
6. A method for manufacturing a polarizing plate, characterized in that: A polarizing plate according to any one of claims 1 to 5 is produced.
7. A display device, characterized in that: A polarizing plate according to any one of claims 1 to 5, The second optical film is arranged on the liquid crystal cell side.